Method of growing plants
A binder composition using oxidized lignins, crosslinking agents, and plasticizers addresses mechanical and water retention issues in plant growth substrates, offering sustainable and efficient plant growth solutions.
Patent Information
- Application Number
- JP2024192353
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
AI Technical Summary
Existing plant growth substrates face challenges with mechanical handling properties, water retention, phytotoxicity, and the use of non-renewable binders, which are costly and environmentally inefficient, particularly due to formaldehyde emissions and the need for additional wetting agents.
A binder composition for plant growth substrates using oxidized lignins, crosslinking agents, and plasticizers, which are formaldehyde-free, improve mechanical strength, water retention, and reduce phytotoxicity, while being based on renewable materials.
The binder composition achieves mechanical properties comparable to phenol-formaldehyde binders, enhances water retention, reduces waste water, and eliminates the need for wetting agents, promoting sustainable and efficient plant growth.
Smart Images

Figure 2025013433000016 
Figure 2025013433000017 
Figure 2025013433000018
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for growing plants using a coherent growth substrate, a coherent growth substrate product, and uses of the coherent growth substrate. [Background technology]
[0002] It has been known for many years to grow plants in coherent growth substrates made from man-made vitreous fiberglass (MMVF). MMVF products used for this purpose are usually provided as coherent plugs, blocks or slabs and generally include a binder to structurally reinforce the product.
[0003] Historically, the primary binders of choice have been phenol-formaldehyde and phenol-formaldehyde urea resins, as disclosed in WO 2009 / 090053, WO 2008 / 009467, WO 2008 / 009462, WO 2008 / 009461, WO 2008 / 009460 and WO 2008 / 009465. These binders are economical to manufacture and have excellent mechanical handling properties, which is very important for plant growth substrates, as automated equipment is used during handling and the substrate retains a lot of water. It is undesirable for the substrate to break during handling or lose rigidity and shape as the substrate retains water.
[0004] However, existing and new legislation directed at reducing or eliminating formaldehyde emissions has led to the development of formaldehyde-free binders, such as those described in WO 2017 / 114723, WO 2017 / 114724 and WO 2012 / 028650.
[0005] At least most of the previously known binder compositions for plant growth substrates are composed of starting materials derived from fossil fuels. There is a continuing trend among consumers to prefer products made entirely or at least partially from renewable materials, and therefore a need exists to provide binders for plant growth substrates made at least partially from renewable materials.
[0006] Binder compositions based on renewable materials have been proposed before, for example in WO 2017 / 114723 and WO 2017 / 114724. However, there are still some disadvantages associated with MMVF products prepared with these binders in terms of mechanical properties when compared with MMVF products prepared with phenol-formaldehyde resins. In addition, such binders are often made from expensive starting materials.
[0007] Additionally, there is a continuing desire to improve the water retention properties of plant growth substrates, such as water retention or distribution of water across the height. There is also a continuing need to reduce the phytotoxicity of binders used in plant growth substrates.
[0008] There is a desire to use water and nutrients as efficiently as possible during the growing process. This is for both cost and environmental reasons. In particular, wastewater containing nutrients is difficult to dispose of due to environmental legislation. It is therefore desirable to improve water retention so that less wastewater (also called drain) is produced.
[0009] Additionally, it would be desirable to reduce the amount and number of components required to produce a plant growth substrate. Generally, additives such as wetting agents are added to plant growth substrates to improve their hydrophilicity. However, from an environmental and cost-effective standpoint, it would be desirable to provide a binder that does not require the addition of additional wetting agents.
[0010] It would also be desirable to produce binders that can be used in smaller amounts than other binders, regardless of mechanical properties. Thus, it would be desirable to produce binders for plant growth substrates that are formaldehyde-free and have mechanical handling properties (e.g., compressive strength) that are comparable or superior to phenol-formaldehyde binders. Such binders would preferably have improved water retention (e.g., water retention, heightwise water distribution), resulting in less water waste and less phytotoxicity. Additionally, it would be desirable for such binders to be economical to produce and based primarily on renewable resources. Finally, it would be desirable for such binders to be reduced in usage and not require the further addition of wetting agents. Summary of the Invention
[0011] The plant growth substrate used in the present invention solves the above problems.
[0012] In a first aspect of the present invention, there is provided a method of growing plants in a coherent growth substrate product, the method comprising: providing at least one coherent growth substrate product comprising man-made vitreous fibers (MMVF) bound with a cured aqueous binder composition; placing one or more seeds, seedlings, cuttings or plants in contact with the growing substrate product; and watering the growing substrate product; The aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0013] In a second aspect of the present invention, there is provided a coherent growth substrate product comprising man-made vitreous fibers (MMVF) combined with a cured aqueous binder composition, the aqueous binder composition prior to curing comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0014] In a third aspect of the present invention, there is provided an array of two or more coherent growth substrate products, said coherent growth substrate products comprising man-made vitreous fibers (MMVF) combined with a cured aqueous binder composition, said aqueous binder composition prior to curing comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0015] In a fourth aspect of the present invention, there is provided a use of a coherent growth substrate product for growing plants, the coherent growth substrate product comprising man-made vitreous fibers (MMVF) combined with a hardened aqueous binder composition, the aqueous binder composition before hardening being: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0016] In a fifth aspect of the present invention, (i) providing an MMVF; (ii) spraying the MMVF with an aqueous binder composition; (iii) recovering and solidifying the MMVF; and (iv) curing the aqueous binder composition; and the aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; A method for producing a growth substrate product is provided, comprising:
[0017] The inventors have surprisingly discovered that it is possible to produce formaldehyde-free binders that result in a growing substrate with mechanical handling properties (e.g., compressive strength) that are comparable to or even better than phenol-formaldehyde binders. The inventors have also produced such binders that result in a growing substrate with improved water retention properties (e.g., water retention) and low phytotoxicity levels, which are highly desirable for plant growth and development. As a result, water waste (drains) can be reduced. The inventors have produced such binders that are economical and based primarily on renewable resources. Finally, the binders can be used in small amounts and do not require the addition of wetting agents to the growing substrate. [Brief description of the drawings]
[0018] [Figure 1A] FIG. 1 shows the results of a compressive strength test. [Figure 1B] FIG. 1 shows the results of a compressive strength test. [Figure 1C] FIG. 1 shows the results of a compressive strength test. [Figure 1D] FIG. 1 shows the results of a compressive strength test. [Figure 1E] FIG. 1 shows the results of a compressive strength test. [Diagram 2] FIG. 1 shows the results of a water retention test. [Diagram 3] FIG. 13 is a diagram showing the results of a moisture distribution test in the height direction. [Figure 4] FIG. 1 shows an example of a cross-section of a lignin structure. [Diagram 5] Lignin precursors and common interunit bonds are shown. [Figure 6] There are four groups of industrial lignins available on the market: [Figure 7] An overview of the properties of industrial lignin is given. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention relates to a method for growing plants in a coherent growth substrate product, the method comprising: providing at least one coherent growth substrate product comprising man-made vitreous fibers (MMVF) bound with a cured aqueous binder composition; placing one or more seeds, seedlings, cuttings or plants in contact with the growing substrate product; and watering the growing substrate product; The aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0020] The method of the present invention includes a coherent growth substrate product comprising man-made vitreous fibers (MMVF). The man-made vitreous fibers (MMVF) can have any suitable oxide composition. The fibers can be glass fibers, ceramic fibers, basalt fibers, slag fibers, or rock or stone fibers. The fibers are preferably of the type commonly known as rock fibers, stone fibers, or slag fibers, and are most preferably stone fibers.
[0021] Stone fibers generally contain the following oxides in weight percentages: SiO2: 30~51 CaO: 8-30 MgO: 2-25 FeO(including Fe2O3): 2~15 Na2O+K2O: 10 or less CaO+MgO: 10-30
[0022] In a preferred embodiment, the MMVF has the following levels of elements, calculated as weight % of oxide: SiO2: at least 30, 32, 35 or 37; not more than 51, 48, 45 or 43 Al2O3: at least 12, 16 or 17; not more than 30, 27 or 25 CaO: at least 8 or 10; not more than 30, 25 or 20 MgO: at least 2 or 5; up to 25, 20, 15 FeO (including Fe2O3): at least 4 or 5; not more than 15, 12 or 10 FeO+MgO: at least 10, 12, 15; not more than 30, 25, 20 Na2O+K2O: 0 or at least 1; 10 or less CaO+MgO: at least 10 or 15; not more than 30 or 25 TiO2: 0 or at least 1; 6, 4 or 2 or less TiO2+FeO: at least 4 or 6; not more than 18 or 12 B2O3: at least 0 or 1; 5 or less than 3 P2O5: 0 or at least 1; 8 or less than 5 Others: 0 or at least 1; 8 or less than 5
[0023] The MMVF produced by the process of the present invention preferably has the following composition in weight percent: SiO235~50 Al2O312~30 TiO2 max 2 Fe2O33~12 CaO 5~30 MgO max 15 Na2O 0~15 K2O 0~15 P2O5 max 3 MnO max 3 B2O3 max 3 has.
[0024] Another preferred composition of MMVF is as follows, in weight percent: SiO2 39-55%, preferably 39-52% Al2O3 16-27%, preferably 16-26% CaO 6-20%, preferably 8-18% MgO 1-5%, preferably 1-4.9% Na2O 0-15%, preferably 2-12% K2O 0-15%, preferably 2-12% R2O(Na2O+K2O) 10-14.7%, preferably 10-13.5% P2O50-3%, preferably 0-2% Fe2O3 (total iron) 3-15%, preferably 3.2-8% B2O3 0-2%, preferably 0-1% TiO20-2%, preferably 0.4-1% Other 0-2.0%
[0025] Glass fibers typically contain the following oxides by weight percent: SiO2: 50-70 Al2O3: 10-30 CaO: 27 or less MgO: 12 or less
[0026] The glass fibers may also contain the following oxides, by weight percent: Na2O+K2O: 8-18, especially Na2O+K2O is more than CaO+MgO. B2O3:3~12
[0027] The glass fiber composition may contain less than 2% Al2O3.
[0028] The geometric mean fiber diameter is often in the range of 1.5 to 10 microns, in particular 2 to 8 microns, preferably 2 to 5 microns. The inventors have found that a geometric mean fiber diameter in this range has a positive effect on the capillary action and thus improves the vertical water distribution and water uptake in the growth substrate.
[0029] The growth substrate according to the present invention, prior to curing, comprises an aqueous binder composition comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Includes.
[0030] In a preferred embodiment, the binder is formaldehyde-free.
[0031] For purposes of this application, the term "formaldehyde-free" means that the formaldehyde emission from a rock wool product is less than 5 μg / m 2 / h or less, preferably 3 μg / m 2 / h. Preferably, the test is performed according to ISO 16000 for aldehyde emission testing.
[0032] Component (i) Component (i) takes the form of one or more oxidized lignins.
[0033] Lignin, cellulose and hemicellulose are the three major organic compounds in plant cell walls. Lignin can be thought of as the glue that holds the cellulose fibers together. Lignin contains both hydrophilic and hydrophobic groups. Lignin is the second most abundant natural polymer in the world after cellulose, and is estimated to account for 20-30% of the total carbon in biomass, with the amount being said to be more than 1 billion tons worldwide.
[0034] FIG. 4 shows an example of a cross-section of a lignin structure.
[0035] There are at least four groups of industrial lignins available on the market. These four groups are shown in Figure 6. A possible fifth group, biorefinery lignins, is a bit different as it is not described on the extraction process but instead on the process origin, e.g. biorefining, and therefore may be similar or different to all of the other groups mentioned. Each group is different from the other and each is suitable for different applications. Lignin is a complex and heterogeneous material containing up to three different phenylpropane monomers, depending on the feedstock. Softwood lignin is made up mostly of coniferyl alcohol units (see Figure 5) and is consequently more homogeneous than hardwood lignin, which has a higher content of syringyl alcohol (see Figure 5). The appearance and viscosity of these lignins are different and highly process dependent.
[0036] A summary of the properties of these industrial lignins is shown in Figure 7.
[0037] Lignosulfonates from the sulfite pulping process remain the largest commercially available source of lignin, with a capacity of 1.4 million tons. However, apart from these, the Kraft process is currently the most used pulping process and is gradually replacing the sulfite process. Kraft pulp production is estimated to produce 78 million tons of lignin annually worldwide, most of which is burned for steam and energy. Current kraft recovery capacity is estimated at 160,000 tons, but sources say current recovery is only about 75,000 tons. Kraft lignin is developed from black liquor, the spent liquor from the sulfate or kraft process. Currently, three well-known processes are employed to produce kraft lignin: LignoBoost, LignoForce, and SLRP. These three processes have in common that they involve the addition of CO2 to lower the pH to 9-10, followed by acidification to lower the pH to about 2. The final step involves a combination of washing, leaching, and filtration to remove ash and other contaminants. All three processes are commercially available in various forms around the world.
[0038] In the Kraft process, thiol groups and stilbenes are introduced, but some carbohydrates remain. Sodium sulfate is also present as an impurity in lignin that precipitates from alcoholic beverages with sulfuric acid, but this may be avoided by changing the lignin isolation method. Since the Kraft process generates a large amount of phenolic hydroxyl groups, lignin becomes soluble in water when these groups are ionized (pH ~10 or higher).
[0039] Commercially available kraft lignin is generally of higher purity than lignosulfonates. Its molecular weight is between 1000 and 3000 g / mol.s. Soda lignin is derived from the sodium hydroxide pulping process and is primarily used for wheat straw, bagasse and flax. The properties of soda lignin are similar to kraft lignin in terms of solubility and Tg. No sulfur is used in the process and there is no covalently bound sulfur. The ash content is very low. Soda lignin has low solubility in neutral and acidic media, but is completely soluble above pH 12.
[0040] The introduction of a large amount of sulfonic acid groups during the lignosulfonation process makes lignin soluble not only in water but also in aqueous acid solutions. Kraft lignin contains 1-2% sulfur, but lignosulfonates contain up to 8% sulfur as sulfonates, most of which are bound to lignin. The molecular weight of lignosulfonates ranges from 15,000 to 50,000 g / mol. This lignin has a higher residual carbohydrate content and a higher average molecular weight than other types. The typical hydrophobic core of lignin and the large number of ionized sulfonate groups make this lignin useful as a surfactant and it is often used to disperse cements and other materials.
[0041] A further group of lignins that are becoming available are those resulting from biorefining processes, where carbohydrates are separated from the lignin by chemical or biochemical processes to produce a carbohydrate-rich fraction. This residual lignin is called biorefinery lignin. Biorefineries focus on producing not only lignin, but also energy and replacements for products derived from fossil fuels and petrochemicals. The lignin resulting from this process is generally considered a low-value product or even a waste product, mainly used for thermal combustion, low-grade feed, or otherwise discarded.
[0042] The feasibility of using organosolv lignin is still being explored on a pilot scale. The process involves extracting lignin by using water together with various organic solvents (most frequently ethanol) and some organic acids. The advantage of this process is the high purity of the lignin obtained, but it is much more expensive than other industrial lignins and has the drawback of being soluble in organic solvents rather than water.
[0043] Attempts to use lignin as a base compound in mineral fiber binder compositions have failed because it has proven difficult to find a suitable cross-linking agent that provides the desired mechanical properties for the cured rock wool product and at the same time is not toxic and / or corrosive. Currently, lignin is used as a replacement for petroleum-derived chemicals such as phenolic resins in binder applications and phenols in asphalt. It is also used as a cement and concrete additive and in some applications as a dispersant.
[0044] Polymer crosslinking generally results in improved properties such as mechanical, chemical and thermal resistance. Lignin is particularly rich in phenolic and aliphatic hydroxyl groups that can undergo reactions leading to crosslinked structures. Some lignins also contain other functional groups that can be utilized. The presence of these functional groups is highly dependent on the method by which the lignin was separated from the cellulose and hemicellulose (thiols in kraft lignin, sulfonates in lignosulfonates, etc.) and also on the source.
[0045] It has now been found that by using oxidized lignin it is possible to prepare a mineral fiber binder composition which is capable of imparting excellent properties to the rock wool product produced.
[0046] In one embodiment, component (i) is in the form of one or more oxidized kraft lignins.
[0047] In one embodiment, component (i) is one or more forms of oxidized soda lignin.
[0048] In one embodiment, component (i) is in the form of one or more ammonia-oxidized lignins. For the purposes of the present invention, the term "ammonia-oxidized lignin" is understood to mean lignin that has been oxidized by an oxidizing agent in the presence of ammonia. The term "ammonia-oxidized lignin" is abbreviated as AOL.
[0049] Alternatively, in an embodiment, ammonia is partially or completely replaced by an alkali metal hydroxide, particularly sodium hydroxide and / or potassium hydroxide.
[0050] A typical oxidizing agent used to prepare oxidized lignin is hydrogen peroxide.
[0051] In one embodiment, the ammonia-oxidized lignin comprises one or more compounds selected from the group of ammonia, amines, hydroxides, or any salt thereof.
[0052] In one embodiment, component (i) has a carboxylic acid group content of 0.05 to 10 mmol / g, for example, 0.1 to 5 mmol / g, for example, 0.20 to 1.5 mmol / g, for example, 0.40 to 1.2 mmol / g, for example, 0.45 to 1.0 mmol / g, based on the dry weight of component (i).
[0053] In one embodiment, component (i) has an average carboxylic acid group content of greater than 1.5 groups per polymer of component (i), such as greater than 2 groups, such as greater than 2.5 groups.
[0054] The carboxylic acid group content of the oxidized lignin is believed to play a key role in providing the surprising advantages of the aqueous mineral fiber binder composition of the present invention, in particular, the carboxylic acid groups of the oxidized lignin are believed to improve crosslinking properties and therefore enable the cured mineral fiber product to develop better mechanical properties.
[0055] Component (ii) Component (ii) takes the form of one or more crosslinking agents.
[0056] In one embodiment, component (ii) comprises one or more crosslinkers selected from β-hydroxyalkylamide crosslinkers and / or oxazoline crosslinkers.
[0057] β-Hydroxyalkylamide crosslinkers are curing agents for acid-functional polymers. They result in crosslinked polymer networks that are hard, durable, corrosion-resistant, and solvent-resistant. β-Hydroxyalkylamide crosslinkers are believed to cure via an esterification reaction that forms multiple ester bonds. The number of hydroxy functional groups on the β-hydroxyalkylamide crosslinkers averages at least 2, preferably greater than 2, and more preferably 2-4, to obtain an optimal curing reaction.
[0058] An oxazoline group-containing crosslinking agent is a polymer containing one or more oxazoline groups in one molecule, and generally, an oxazoline group-containing crosslinking agent can be easily obtained by polymerizing an oxazoline derivative. The patent US Pat. No. 6,818,699 (B2) specification discloses such a process.
[0059] In one embodiment, component (ii) is an epoxidized oil based on fatty acid triglycerides.
[0060] Epoxidized oils based on fatty acid triglycerides are not considered hazardous materials, therefore, the use of these compounds for the binder compositions of the present invention means that these compositions do not have to be treated as hazardous materials.
[0061] In one embodiment, component (ii) is a molecule having three or more epoxy groups.
[0062] In one embodiment, component (ii) is one or more flexible oligomers or polymers, such as low Tg acrylic polymers, low Tg vinyl polymers, low Tg polyethers, which contain reactive functional groups, such as carbodiimide groups, such as acid anhydrides, such as oxazoline groups, such as amino groups, such as epoxy groups, and the like.
[0063] In one embodiment, component (ii) is selected from the group consisting of crosslinkers participating in the curing reaction, such as hydroxyalkylamides, alkanolamines, reaction products of alkanolamines with polycarboxylic acids, which are described in US Pat. No. 6,706,853 B1.
[0064] Without wishing to be bound by any particular theory, the inventors believe that the non- The consistently advantageous properties are believed to be due to the interaction of the oxidized lignin used as component (i) with the crosslinking agents described above. The presence of carboxylic acid groups on the oxidized lignin allows the oxidized lignin to crosslink very effectively.
[0065] In one embodiment, component (ii) is one or more crosslinkers selected from the group consisting of polyfunctional organic amines such as alkanolamines, diamines such as hexamethyldiamine, triamines, and the like.
[0066] In one embodiment, component (ii) is one or more crosslinkers selected from the group consisting of polyethyleneimines, polyvinylamines, and aliphatic amines.
[0067] In one embodiment, component (ii) is one or more aliphatic amides.
[0068] In one embodiment, component (ii) is one or more crosslinkers selected from the group consisting of dimethoxyethanal, glycolaldehyde, glyoxylic acid.
[0069] In one embodiment, component (ii) is one or more crosslinkers selected from polyester polyols, such as polycaprolactone.
[0070] In one embodiment, component (ii) is one or more crosslinkers selected from the group consisting of starch, modified starch, CMC.
[0071] In one embodiment, component (ii) is one or more crosslinkers in the form of an aliphatic polyfunctional carbodiimide.
[0072] In one embodiment, component (ii) is one or more crosslinkers selected from melamine-based crosslinkers, such as hexakis(methylmethoxy)melamine (HMMM)-based crosslinkers.
[0073] Examples of such compounds include Picassian XL 701, 702, 725 (Stahl Polymers), ZOLDINE® XL-29SE (Angus Chemical Company), CX300 (DSM), Carbodilite V-02-12 (Nisshinbo Chemical Inc.), and the like.
[0074] Component (ii) can also be a mixture of any of the above compounds.
[0075] In one embodiment, the binder composition according to the present invention comprises component (ii) in an amount of 1 to 40% by weight, such as 4 to 20% by weight, such as 6 to 12% by weight, based on the dry weight of component (i).
[0076] Ingredient (iii) Component (iii) takes the form of one or more plasticizers.
[0077] In one embodiment, component (iii) is a polyol, such as a carbohydrate, a hydrogenated sugar, such as sorbitol, erythritol, glycerol, monoethylene glycol, polyethylene glycol, polyethylene glycol ethers, polyethers, phthalates and / or acids, such as adipic acid, vanillic acid, lactic acid and / or ferulic acid, acrylic polymers, polyvinyl alcohol, polyurethane dispersions, ethylene carbonate, propylene carbonate, lactones, lactams, lactides, acrylics with free carboxy groups. It takes the form of a polymer and / or one or more plasticizers selected from the group consisting of polyurethane dispersions having free carboxy groups, polyamides, amides such as carbamide / urea, or any mixtures thereof.
[0078] In one embodiment, component (iii) takes the form of one or more plasticizers selected from the group consisting of carbonates, e.g. ethylene carbonate, propylene carbonate, lactones, lactams, lactides, compounds having a structure similar to lignin, such as vanillin, acetosyringone, solvents used as coalescents, such as alcohol ethers, polyvinyl alcohol, etc.
[0079] In one embodiment, component (iii) takes the form of one or more non-reactive plasticizers selected from the group consisting of polyethylene glycols, polyethylene glycol ethers, polyethers, hydrogenated sugars, phthalates and / or other esters, solvents used as coalescents such as alcohol ethers, acrylic polymers, polyvinyl alcohol.
[0080] In one embodiment, component (iii) is one or more reactive plasticizers selected from the group consisting of carbonates, such as ethylene carbonate, propylene carbonate, lactones, lactams, lactides, di- or tricarboxylic acids, such as adipic acid, or lactic acid, and / or vanillic acid and / or ferulic acid, polyurethane dispersions, acrylic polymers with free carboxy groups, compounds with a structure similar to lignin, such as vanillin, acetosyringone.
[0081] In one embodiment, component (iii) takes the form of one or more plasticizers selected from the group consisting of fatty alcohols, monohydroxy alcohols such as pentanol, and stearyl alcohol.
[0082] In one embodiment, component (iii) comprises one or more forms of plasticizers selected from the group consisting of polyethylene glycols and polyethylene glycol ethers.
[0083] Another particularly surprising aspect of the present invention is the significant improvement in the mechanical properties of the mineral fibre products according to the invention due to the use of plasticisers having a boiling point above 100°C, in particular between 140 and 250°C, which, in view of their boiling point, appear to evaporate at least partially during the hardening of the aqueous binder in contact with the mineral fibres.
[0084] In one embodiment, component (iii) comprises one or more plasticizers having a boiling point above 100°C, for example from 110 to 280°C, more preferably from 120 to 260°C, more preferably from 140 to 250°C.
[0085] The effectiveness of these plasticizers in aqueous binder compositions is believed to be due to their ability to improve the mobility of oxidized lignin during the curing process, which is believed to effectively promote crosslinking.
[0086] In one embodiment, component (iii) comprises one or more polyethylene glycols having an average molecular weight of 150 to 50000 g / mol, in particular 150 to 4000 g / mol, more particularly 150 to 1000 g / mol, preferably 150 to 500 g / mol, more preferably 200 to 400 g / mol.
[0087] In one embodiment, component (iii) comprises one or more polyethylene glycols having an average molecular weight of 4000 to 25000 g / mol, in particular 4000 to 15000 g / mol, more particularly 8000 to 12000 g / mol.
[0088] In one embodiment, component (iii) is capable of forming a covalent bond with component (i) and / or component (ii) during the curing process. Such components will not evaporate and remain as part of the composition, but will be effectively modified so as not to cause undesirable side effects in the cured product, such as water absorption. Non-limiting examples of such components include caprolactone and acrylic polymers with free carboxyl groups.
[0089] In one embodiment, component (iii) is selected from the group consisting of aliphatic alcohols, monohydroxy alcohols such as pentanol, stearyl alcohol, and the like.
[0090] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of alkoxylates, such as ethoxylates, such as butanol ethoxylate, such as butoxytriglycol.
[0091] In one embodiment, component (iii) is selected from one or more propylene glycols.
[0092] In one embodiment, component (iii) is selected from one or more glycol esters.
[0093] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of adipates, acetates, benzoates, cyclobenzoates, citrates, stearates, sorbates, sebacates, azelates, butyrates, and valerates.
[0094] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of phenol derivatives, such as alkyl or aryl substituted phenols.
[0095] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of silanols and siloxanes.
[0096] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of sulfates, such as alkyl sulfates; sulfonates, such as alkylaryl sulfonates, such as alkyl sulfonates; and phosphates, such as tripolyphosphates, such as tributyl phosphate.
[0097] In one embodiment, component (iii) is selected from one or more hydroxy acids.
[0098] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of monomeric amides, such as acetamides, benzamides, fatty acid amides, such as tall oil amides.
[0099] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of quaternary ammonium compounds, such as trimethylglycine, distearyldimethylammonium chloride, and the like.
[0100] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of vegetable oils such as castor oil, palm oil, linseed oil, tall oil, soybean oil, and the like.
[0101] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of hydrogenated oils and acetylated oils.
[0102] In one embodiment, component (iii) is selected from one or more fatty acid methyl esters.
[0103] In one embodiment, component (iii) is selected from one or more plasticizers selected from the group consisting of alkyl polyglucosides, gluconamides, aminoglucosamides, sucrose esters, and sorbitan esters.
[0104] Surprisingly, it has been found that the inclusion of a plasticizer in the aqueous binder composition significantly improves the mechanical properties of the growth substrate according to the present invention.
[0105] The term plasticizer refers to a substance that is added to a material to make it softer, more flexible (by lowering the glass transition temperature, Tg), and easier to process.
[0106] Component (iii) can also be a mixture of any of the above compounds.
[0107] In one embodiment, component (iii) is present in an amount from 0.5 to 50% by weight, preferably from 2.5 to 25% by weight, more preferably from 3 to 15% by weight, based on the dry weight of component (i).
[0108] Aqueous binder composition for mineral fibres comprising components (i) and (iia) One embodiment of the present invention comprises: Component (i) in the form of one or more oxidized lignins; Component (iia) in the form of one or more modifiers, The present invention relates to an aqueous binder composition for mineral fibers comprising:
[0109] The inventors have found that excellent binder properties can also be achieved with a two-component system comprising component (i) in the form of one or more oxidized lignins and component (iia) in the form of one or more modifiers, and optionally any of the other components described above and below.
[0110] In one embodiment, component (iia) is a modifier in the form of one or more compounds selected from the group consisting of epoxidized oils based on fatty acid triglycerides.
[0111] In one embodiment, component (iia) is a modifier in the form of one or more compounds selected from molecules having three or more epoxy groups.
[0112] In one embodiment, component (iia) is one or more flexible oligomers or polymers, e.g. modifiers in the form of low Tg acrylic polymers, low Tg vinyl polymers, e.g. low Tg polyethers, etc., comprising reactive functional groups such as carbodiimide groups, e.g. anhydride groups, e.g. oxazoline groups, e.g. amino groups, e.g. epoxy groups.
[0113] In one embodiment, component (iia) is one or more modifiers selected from the group consisting of polyethyleneimines, polyvinylamines, and aliphatic amines.
[0114] In one embodiment, component (iia) is one or more modifiers selected from aliphatic polyfunctional carbodiimides.
[0115] Component (iia) can also be a mixture of any of the compounds mentioned above.
[0116] Without wishing to be bound by any particular theory, the inventors believe that excellent binder properties are due to the incorporation of components (i) and (iia) and optionally further components in a binder for mineral fibers. It is believed that the benefits achieved by the undercoat composition are due, at least in part, to the effect that the modifier employed as component (iia) functions as both a plasticizer and a crosslinker.
[0117] In one embodiment, the aqueous binder composition comprises component (iia) in an amount of from 1 to 40% by weight, such as from 4 to 20% by weight, for example from 6 to 12% by weight, based on the dry weight of component (i).
[0118] Further ingredients In some embodiments, the aqueous binder composition includes additional components.
[0119] In one embodiment, the aqueous binder composition comprises an inorganic acid, such as sulfuric acid, sulfamic acid, nitric acid, boric acid, hypophosphorous acid, and / or phosphoric acid, and / or any salt thereof, such as sodium hypophosphite, and / or an ammonium salt, such as the ammonium salt of sulfuric acid, sulfamic acid, nitric acid, boric acid, hypophosphorous acid, and / or phosphoric acid. The presence of such a catalyst can improve the curability of the aqueous binder composition.
[0120] In one embodiment, the aqueous binder composition may be, for example, ZnCl, Mg(ClO), Sn[N(SO-n-C8F 17 )2]4, and the like.
[0121] In one embodiment, the aqueous binder composition includes a catalyst selected from metal chlorides such as KCl, MgCl2, ZnCl2, FeCl3, and SnCl2.
[0122] In one embodiment, the aqueous binder composition includes a catalyst selected from organometallic compounds such as titanate-based catalysts and stannum-based catalysts.
[0123] In one embodiment, the aqueous binder composition includes a chelating agent, such as a catalyst selected from transition metals, such as iron ions, chromium ions, manganese ions, copper ions, and the like.
[0124] In one embodiment, the aqueous binder composition comprises a further component (iv) in the form of one or more silanes.
[0125] In one embodiment, the aqueous binder composition comprises a further component (iv) in the form of one or more coupling agents, such as organofunctional silanes.
[0126] In one embodiment, component (iv) is selected from the group consisting of organofunctional silanes, such as primary or secondary amino-functional silanes, epoxy-functional silanes, such as polymeric or oligomeric epoxy-functional silanes, methacrylate-functional silanes, alkyl- and aryl-functional silanes, urea-functional silanes or vinyl-functional silanes.
[0127] In one embodiment, the aqueous binder composition further comprises component (v) in the form of one or more selected from the group of ammonia, an amine, or any salt thereof.
[0128] The inventors have found that the inclusion of ammonia, an amine or any salt thereof as a further component is useful, particularly when oxidized lignin is used in component (i), which oxidized lignin has not been oxidized in the presence of ammonia.
[0129] In one embodiment the aqueous binder composition further comprises a further component in the form of urea, especially in an amount of 5 to 40% by weight, for example 10 to 30% by weight, 15 to 25% by weight, based on the dry weight of component (i).
[0130] In one embodiment, the aqueous binder composition comprises a further component in the form of one or more sugars selected from the group consisting of sucrose, reducing sugars, in particular dextrose, polysaccharides and mixtures thereof, preferably dextrins and maltodextrins, more preferably glucose syrup, even more preferably glucose syrup having a dextrose equivalent value DE=30-<100, such as DE=60-<100, for example DE=60-99, such as DE=85-99, for example DE=95-99.
[0131] In one embodiment the aqueous binder composition comprises a further component in the form of one or more carbohydrates selected from the group consisting of sucrose and reducing sugars in an amount of 5 to 50% by weight, such as 5 to less than 50% by weight, for example 10 to 40% by weight, such as 15 to 30% by weight, based on the dry weight of component (i).
[0132] In the context of the present invention, a binder composition having a sugar content of 50% or more by weight, based on the total dry weight of the binder components, is considered to be a sugar-based binder. In the context of the present invention, a binder composition having a sugar content of less than 50% by weight, based on the total dry weight of the binder components, is considered to be a non-sugar-based binder.
[0133] In one embodiment, the aqueous adhesive comprises further components in the form of one or more surfactants in the form of non-ionic and / or ionic emulsifiers, such as, for example, polyoxyethylene (4) lauryl ether, soy lecithin, for example, sodium dodecyl sulfate.
[0134] In one embodiment, the aqueous binder composition comprises: Component (i) in the form of one or more ammonia-oxidized lignins having a carboxylic acid group content of from 0.05 to 10 mmol / g, such as from 0.1 to 5 mmol / g, for example from 0.20 to 1.5 mmol / g, such as from 0.40 to 1.2 mmol / g, for example from 0.45 to 1.0 mmol / g, based on the dry weight of component (i). Component (ii) in the form of one or more crosslinkers selected from β-hydroxyalkylamide crosslinkers and / or oxazoline crosslinkers, and / or one or more crosslinkers selected from the group consisting of alkanolamines, diamines, e.g. hexamethyldiamine, triamines, and other polyfunctional organic amines. Component (iii) in the form of one or more polyethylene glycols having an average molecular weight of 150 to 50000 g / mol, in particular 150 to 4000 g / mol, more in particular 150 to 1000 g / mol, preferably 150 to 500 g / mol, more preferably 150 to 300 g / mol, or in the form of one or more polyethylene glycols having an average molecular weight of 4000 to 25000 g / mol, in particular 4000 to 15000 g / mol, more in particular 8000 to 12000 g / m, wherein preferably the aqueous binder composition comprises component (ii) in an amount of 1 to 40% by weight, for example 4 to 20% by weight, for example 6 to 12% by weight, based on the dry weight of component (i), and (iii) is present in an amount of 0.5 to 50% by weight, preferably 2.5 to 25% by weight, more preferably 3 to 15% by weight, based on the dry weight of component (i).
[0135] In one embodiment, the aqueous binder composition comprises: Component (i) in the form of one or more ammonia-oxidized lignins containing 0.05 to 10 mmol / g, such as 0.1 to 5 mmol / g, for example 0.20 to 1.5 mmol / g, such as 0.40 to 1.2 mmol / g, for example 0.45 to 1.0 mmol / g, of carboxylic acid groups, based on the dry weight of component (i). Component (iia) in the form of one or more modifiers selected from epoxidized oils based on fatty acid triglycerides.
[0136] In one embodiment, the aqueous binder composition comprises: Component (i) in the form of one or more ammonia-oxidized lignins having an average carboxylic acid group content of greater than 1.5 groups per polymer of component (i), such as greater than 2 groups, such as greater than 2.5 groups. Component (ii) in the form of one or more crosslinkers selected from β-hydroxyalkylamide crosslinkers and / or oxazoline crosslinkers, and / or component (ii) in the form of one or more crosslinkers selected from the group consisting of alkanolamines, diamines, e.g. hexamethyldiamine, triamines and other polyfunctional organic amines. Component (iii) in the form of one or more polyethylene glycols having an average molecular weight of 150 to 50000 g / mol, in particular 150 to 4000 g / mol, more in particular 150 to 1000 g / mol, preferably 150 to 500 g / mol, more preferably 150 to 300 g / mol, or in the form of one or more polyethylene glycols having an average molecular weight of 4000 to 25000 g / mol, in particular 4000 to 15000 g / mol, more in particular 8000 to 12000 g / m, wherein preferably the aqueous binder composition comprises an amount of component (ii) of 1 to 40% by weight, for example 4 to 20% by weight, for example 6 to 12% by weight, based on the dry weight of component (i), and (iii) is present in an amount of 0.5 to 50, preferably 2.5 to 25, more preferably 3 to 15% by weight, based on the dry weight of component (i).
[0137] In one embodiment, the aqueous binder composition comprises: Component (i) in the form of one or more ammonia-oxidized lignins having an average carboxylic acid group content of greater than 1.5 groups per polymer of component (i), such as greater than 2 groups, such as greater than 2.5 groups. Component (iia) in the form of one or more modifiers selected from epoxidized oils based on fatty acid triglycerides.
[0138] In one embodiment, the aqueous binder composition comprises essentially Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Component (iv) in the form of one or more coupling agents, such as organofunctional silanes; Optionally, a component in the form of one or more compounds selected from the group of ammonia, amines or salts thereof; Optionally, a component in the form of urea; Optionally, a component in the form of a more reactive or non-reactive silicone; Optionally, a hydrocarbon oil; optionally one or more surfactants; water, It consists of:
[0139] In one embodiment, the aqueous binder composition comprises essentially Component (i) in the form of one or more oxidized lignins; component (iia) in the form of one or more modifiers selected from epoxidized oils based on fatty acid triglycerides; Component (iv) in the form of one or more coupling agents, such as organofunctional silanes; Optionally, a component in the form of one or more compounds selected from the group of ammonia, amines or salts thereof; Optionally, a component in the form of urea; Optionally, a component in the form of a more reactive or non-reactive silicone; Optionally, a hydrocarbon oil; optionally one or more surfactants; water; It consists of:
[0140] The growing substrate preferably comprises from 1.0% to 6.0% by weight of the cured binder composition, preferably from 2.0% to 4.5% by weight, most preferably from 2.5% to 3.5% by weight, based on the weight of the growing substrate. The binder content is measured according to DS / EN13820:2003. The binder content is taken as the loss on ignition. The binder content includes any binder additives.
[0141] The oxidized lignin in the aqueous binder composition can be prepared as follows.
[0142] Method I for preparing oxidized lignin The oxidized lignin that can be used as a component of the binder used in the present invention is One or more lignin-containing components (a); Component (b) comprising ammonia, one or more amine components, and / or salts thereof; Component (c) containing one or more oxidizing agents; The compound can be prepared by a process comprising contacting
[0143] Component (a) Component (a) comprises one or more lignins.
[0144] In one embodiment, component (a) comprises one or more kraft lignins, one or more soda lignins, one or more lignosulfonate lignins, one or more organosolv lignins, lignins from a biorefining process of a lignocellulosic feedstock, or any mixture thereof.
[0145] In one embodiment, component (a) comprises one or more kraft lignins.
[0146] Ingredient (b) In one embodiment, component (b) comprises ammonia, one or more amino components, and / or any salts thereof. Without wishing to be bound by any particular theory, the inventors believe that the replacement of the alkali hydroxides used in conventionally known oxidative treatments of lignin with ammonia, one or more amino components, and / or any salts thereof plays an important role in improving the properties of the oxidized lignin prepared according to the method of the present invention.
[0147] The inventors have surprisingly found that lignin oxidized with an oxidizing agent in the presence of ammonia or an amine contains a significant amount of nitrogen as part of the oxidized lignin's structure. Without wishing to be bound by any particular theory, the inventors believe that the improved fire resistance properties of the oxidized lignin prepared by the methods described herein when used in products that include the oxidized lignin in a binder composition are due, at least in part, to the nitrogen in the oxidized lignin's structure.
[0148] In one embodiment, component (b) comprises ammonia and / or any salt thereof.
[0149] Without wishing to be bound by any particular theory, the inventors believe that the improved stability characteristics of the derivatized lignins prepared according to the present invention are due, at least in part, to the fact that ammonia is a volatile compound and can be evaporated or easily removed and reused from the final product, in contrast to the fact that it has proven difficult to remove residual alkali hydroxides used in previously known oxidation processes.
[0150] Nevertheless, component (b) may contain ammonia, one or more amino components, and / or In addition to any salts thereof, it may be advantageous in the process to include relatively small amounts of alkali and / or earth alkali metal hydroxides, such as sodium hydroxide and / or potassium hydroxide.
[0151] In embodiments in which component (b) comprises, in addition to ammonia, one or more amino components, and / or any salts thereof, a component that is an alkali and / or earth alkali metal hydroxide, such as sodium hydroxide and / or potassium hydroxide, the amount of alkali and / or earth alkali metal hydroxide will typically be in the order of 5 to 70 parts by weight, e.g., 10 to 20 parts by weight, of the alkali and / or earth alkali metal hydroxide, based on the ammonia.
[0152] Ingredient (c) In the methods described herein, component (c) comprises one or more oxidizing agents.
[0153] In one embodiment, component (c) comprises one or more oxidizing agents in the form of hydrogen peroxide, an organic or inorganic peroxide, molecular oxygen, ozone, air, a halogen-containing oxidizing agent, or any mixture thereof.
[0154] In the early stages of oxidation, active radicals from the oxidizing agent typically abstract a proton from a phenolic group, since this bond has the lowest dissociation energy in lignin. Lignin stabilizes the radicals through mesomerics and has multiple pathways to continue (and terminate) the reaction, resulting in a variety of intermediate and final products. Depending on this complexity (and the conditions chosen), the average molecular weight can increase and decrease, and in our experiments we have observed modest increases in average molecular weight, typically around 30%.
[0155] In one embodiment, component (c) comprises hydrogen peroxide.
[0156] Hydrogen peroxide is perhaps the most commonly employed oxidizing agent due to its overlapping low cost, good efficiency, and relatively low level of environmental impact. When hydrogen peroxide is used without a catalyst, alkaline conditions and temperature are important, as the following reactions occur leading to radical formation:
[0157] [ka]
[0158] The inventors have found that the derivatized lignins prepared by the methods described herein contain increased amounts of carboxylic acid groups as a result of the oxidation process. Without wishing to be bound by any particular theory, the inventors believe that the carboxylic acid group content of the oxidized lignin prepared in this process plays an important role in the desirable reactivity properties of the derivatized lignins prepared by the methods described herein.
[0159] Another advantage of the oxidation process is that the oxidized lignin is more hydrophilic, which can increase its solubility in water and promote adhesion to polar substrates such as mineral fibers.
[0160] Further ingredients In one embodiment, the process for preparing oxidized lignin preferably contains further components, in particular component (d), in the form of an oxidation catalyst, such as one or more transition metal catalysts, such as ferrous sulfate, e.g. manganese, palladium, selenium, tungsten containing catalysts, and the like.
[0161] Such oxidation catalysts can increase the rate of the reaction, thereby improving the properties of the oxidized lignin.
[0162] Mass ratio of components One skilled in the art will use components (a), (b) and (c) in their respective relative amounts such that the desired degree of oxidation of lignin is achieved.
[0163] In one embodiment, Component (a) comprises one or more lignins; component (b) contains ammonia, Component (c) comprises one or more oxidizing agents in the form of hydrogen peroxide; Here, the mass ratio of lignin, ammonia, and hydrogen peroxide is such that the amount of ammonia is 0.01 to 0.5 parts by weight, for example, 0.1 to 0.3, for example, 0.15 to 0.25 parts by weight, based on the dry weight of lignin, and the amount of hydrogen peroxide is 0.025 to 1.0 parts by weight, for example, 0.05 to 0.2 parts by weight, for example, 0.075 to 0.125 parts by weight, based on the dry weight of lignin.
[0164] process There is one or more possibilities for contacting components (a), (b) and (c) to effect the desired oxidation reaction.
[0165] In one embodiment, the method comprises the steps of: providing component (a) in the form of an aqueous solution and / or dispersion of one or more lignins, the aqueous solution having a lignin content of 1 to 50% by weight, such as 5 to 25% by weight, for example 15 to 22% by weight, for example 18 to 20% by weight, based on the total weight of the aqueous solution; adjusting the pH by adding component (b) comprising an aqueous solution of ammonia, one or more amine components, and / or salts thereof; an oxidation step of adding component (c) containing an oxidizing agent; Includes.
[0166] In one embodiment, the pH adjustment step is carried out such that the pH of the resulting aqueous solution and / or dispersion is pH≧9, such as ≧10, for example ≧10.5.
[0167] In one embodiment, the pH adjustment step is carried out so that the pH of the resulting aqueous solution and / or dispersion is within the range of 10.5-12.
[0168] In one embodiment, the pH adjustment step is carried out by increasing the temperature to ≧25°C and then controlling it to a range of 25-50°C, for example 30-45°C, for example 35-40°C.
[0169] In one embodiment, during the oxidation step, the temperature is increased to ≧35°C and then controlled in the range of 35-150°C, such as 40-90°C, for example 45-80°C.
[0170] In one embodiment, the oxidation step is carried out for a time period between 1 second and 48 hours, such as between 10 seconds and 36 hours, such as between 1 minute and 24 hours, such as between 2 and 5 hours.
[0171] Method II for preparing oxidized lignin The oxidized lignin used as a component of the binder used in the present invention is One or more lignin-containing components (a); Ammonia and / or one or more amine components and / or their salts, alkali and / or or an alkaline earth metal hydroxide, such as sodium hydroxide and / or potassium hydroxide; component (c) comprising one or more oxidizing agents; Component (d) in the form of one or more plasticizers; The compound can be prepared by a process comprising contacting
[0172] Component (a) Component (a) comprises one or more lignins.
[0173] In one embodiment of the method for preparing oxidized lignin, component (a) comprises one or more kraft lignins, one or more soda lignins, one or more lignosulfonate lignins, one or more organosolv lignins, lignins obtained in a biorefining process of a lignocellulosic feedstock, or any mixture thereof.
[0174] In one embodiment, component (a) comprises one or more kraft lignins.
[0175] Ingredient (b) In one embodiment of preparing oxidized lignin, component (b) comprises ammonia, one or more amino components, and / or any salts thereof, and / or alkali and / or alkaline earth metal hydroxides, such as sodium hydroxide and / or potassium hydroxide.
[0176] "Ammonia-oxidized lignin" is understood as lignin that has been oxidized by an oxidizing agent in the presence of ammonia. The term "ammonia-oxidized lignin" is abbreviated as AOL.
[0177] In one embodiment, component (b) comprises ammonia and / or any salt thereof.
[0178] Without wishing to be bound by any particular theory, the inventors believe that the improved stability of derivatized lignins prepared according to the present invention using ammonia and / or any salts thereof, component (b), is due, at least in part, to the fact that ammonia is a volatile compound and therefore can be evaporated or easily removed from the final product and reused.
[0179] Nevertheless, in this embodiment of the process for the preparation of oxidized lignin, it may be advantageous for component (b) to comprise, in addition to ammonia, one or more amino components, and / or any salts thereof, relatively small amounts of alkali metal and / or alkaline earth metal hydroxides, such as sodium hydroxide and / or potassium hydroxide.
[0180] In an embodiment in which component (b) contains, in addition to ammonia, one or more amino components, and / or any salt thereof, an alkali and / or alkaline earth metal hydroxide, such as sodium hydroxide and / or potassium hydroxide, the amount of alkali and / or alkaline earth metal hydroxide added is small, typically 5 to 70 parts by weight, for example 10 to 20 parts by weight, based on the ammonia.
[0181] Ingredient (c) In the process for preparing oxidized lignin, component (c) comprises one or more oxidizing agents.
[0182] In one embodiment, component (c) comprises one or more oxidizing agents in the form of hydrogen peroxide, an organic or inorganic peroxide, molecular oxygen, ozone, air, a halogen-containing oxidizing agent, or any mixture thereof.
[0183] In the early stages of oxidation, active radicals from the oxidant typically abstract protons from phenolic groups, as this bond has the lowest dissociation energy in lignin. Lignin can stabilize the radicals by mesomericism, so there are multiple pathways to continue (terminate) the reaction, which gives rise to a variety of intermediate and final products. The average molecular weight can increase and decrease due to this complexity (and the conditions chosen), and in our experiments we have typically seen reasonable increases in average molecular weight of about 30%.
[0184] In one embodiment, component (c) comprises hydrogen peroxide.
[0185] Hydrogen peroxide is perhaps the most commonly employed oxidizing agent due to its overlapping low cost, good efficiency, and relatively low level of environmental impact. When hydrogen peroxide is used without a catalyst, alkaline conditions and temperature are important, as the following reactions occur leading to radical formation:
[0186] [ka]
[0187] The inventors have found that the derivatized lignins prepared by the methods described herein contain increased amounts of carboxylic acid groups as a result of the oxidation process. Without wishing to be bound by any particular theory, the inventors believe that the carboxylic acid group content of the oxidized lignins prepared by the processes according to the invention plays an important role in the desired reactivity properties of the derivatized lignins prepared by the methods described herein.
[0188] Another advantage of the oxidation process is that the oxidized lignin is more hydrophilic, which can increase its solubility in water and promote adhesion to polar substrates such as mineral fibers.
[0189] Ingredient (d) Component (d) comprises one or more plasticizers.
[0190] In one embodiment, component (d) is one or more plasticizers in the form of: Polyols, such as carbohydrates, hydrogenated sugars, such as sorbitol, erythritol, glycerol, monoethylene glycol, polyethylene glycol, polyethylene glycol ethers, polyethers, phthalic acid esters and / or acids, such as adipic acid, vanillic acid, lactic acid and / or ferulic acid, acrylic polymers, polyvinyl alcohol, polyurethane dispersions, ethylene carbonate, propylene carbonate, lactones, lactams, lactides, acrylic polymers with free carboxyl groups and / or polyurethane dispersions with free carboxyl groups, polyamides, amides such as carbamide / urea, or any mixtures thereof.
[0191] The inventors have found that the inclusion of component (d) in the form of one or more plasticizers results in a reduction in the viscosity of the reaction mixture, thereby enabling a highly efficient method of producing oxidized lignin.
[0192] In one embodiment according to the invention, component (d) is one or more plasticizers: polyols, such as carbohydrates, hydrogenated sugars, such as sorbitol, erythritol, glycerol, monoethylene glycol, polyethylene glycol, polyvinyl alcohol, acrylic polymers with free carboxy groups and / or polyurethane dispersions with free carboxy groups. The polymers may be in the form of a polymeric polymer, such as a liquid, a polyamide, an amide such as carbamide / urea, or any mixture thereof.
[0193] In one embodiment according to the present invention, component (d) comprises one or more plasticizers selected from the group of polyethylene glycol, polyvinyl alcohol, urea or any mixture thereof.
[0194] Further ingredients In one embodiment, the process for preparing oxidized lignin preferably comprises a further component, in particular component (v) in the form of an oxidation catalyst, such as one or more transition metal catalysts, such as iron sulfate, e.g. manganese, palladium, selenium, tungsten containing catalysts, and the like.
[0195] Such oxidation catalysts can increase the rate of the reaction, thereby improving the properties of the oxidized lignin prepared by the present method.
[0196] Mass ratio of components Those skilled in the art will employ components (a), (b), (c) and (d) in such relative amounts as to achieve the desired degree of oxidation of the lignin.
[0197] In one embodiment, the method comprises: Component (a) comprises one or more lignins; component (b) comprises ammonia; component (c) comprises one or more oxidizing agents in the form of hydrogen peroxide; Component (d) is one or more plasticizers selected from the group of polyethylene glycols; and Here, the mass ratio of lignin, ammonia, hydrogen peroxide and polyethylene glycol is such that the amount of ammonia is 0.01-0.5 parts by weight, for example 0.1-0.3, for example 0.15-0.25 parts by weight (25% by weight solution in water) based on the dry weight of lignin, and the amount of hydrogen peroxide (30% by weight solution in water) is 0.025-1.0 parts by weight, for example 0.07-0.50 parts by weight, for example 0.15-0.30 parts by weight of hydrogen peroxide based on the dry weight of lignin, and the amount of polyethylene glycol is 0.03-0.60 parts by weight, for example 0.07-0.50 parts by weight, for example 0.10-0.40 parts by weight of polyethylene glycol based on the dry weight of lignin.
[0198] For purposes of the present invention, "dry weight of lignin" is preferably defined as the weight of the lignin in the form in which it is provided.
[0199] process There is more than one possibility for contacting components (a), (b), (c), and (d) to achieve the desired oxidation reaction.
[0200] In one embodiment, the method comprises: providing component (a) in the form of an aqueous solution and / or dispersion of one or more lignins, the aqueous solution having a lignin content of from 5 to 90% by weight, such as from 10 to 85% by weight, such as from 15 to 70% by weight, based on the total weight of the aqueous solution; adding component (b) to adjust the pH; adding component (d); an oxidation step of adding component (c) containing an oxidizing agent; Includes.
[0201] In one embodiment, the pH adjustment step is carried out so that the pH of the resulting aqueous solution and / or dispersion is p H≧9, such as ≧10, for example ≧10.5.
[0202] In one embodiment, the pH adjustment step is carried out so that the pH of the resulting aqueous solution and / or dispersion is within the range of 9.5 to 12.
[0203] In one embodiment, the pH adjustment step is carried out by increasing the temperature to ≧25°C, and then controlling the temperature within the range of 25 to 50°C, for example, 30 to 45°C, for example, 35 to 40°C.
[0204] In one embodiment, during the oxidation step, the temperature is increased to ≧35°C and then controlled in the range of 35-150°C, such as 40-90°C, for example 45-80°C.
[0205] In one embodiment, the oxidation step is carried out for a period of time between 1 second and 24 hours, such as between 1 minute and 12 hours, such as between 10 minutes and 8 hours, such as between 5 minutes and 1 hour.
[0206] The inventors have found that the process described herein can produce a reaction mixture with a high dry matter content, and therefore a high throughput can be achieved in the process according to the invention, where the reaction product in the form of oxidized lignin can be used as a component of industrial mass-produced products, such as mineral fiber products.
[0207] In one embodiment, the process is carried out such that the dry matter content of the reaction mixture is from 20 to 80% by weight, such as from 40 to 70% by weight.
[0208] In one embodiment, the method is carried out such that the viscosity of the oxidized lignin is between 100 cP and 100,000 cP, such as between 500 cP and 50,000 cP, such as between 1,000 cP and 25,000 cP.
[0209] For purposes of this invention, viscosity is dynamic viscosity and is defined as the resistance of a liquid / paste to change shape or to relative movement with adjacent parts. Viscosity is measured in centipoise (cP), which is equivalent to 1 mPa·s (milliPascal·second). Viscosity is measured at 20°C using a viscometer. For purposes of this invention, dynamic viscosity can be measured at 20°C using a Wells-Brookfield viscometer of the cone-plate type.
[0210] In one embodiment, the method is performed to include a rotor / stator arrangement.
[0211] In one embodiment, the method is carried out as a continuous or semi-continuous process.
[0212] Apparatus for carrying out the method The invention also relates to an apparatus for carrying out the above method.
[0213] In one embodiment, an apparatus for performing the method comprises: rotor / stator arrangement; A premixing apparatus for components (a), (b) and (d); one or more inlets for water, components (a), (b), (c), and (d); one or more outlets for the oxidized lignin; Includes.
[0214] In one embodiment, the apparatus is configured such that an inlet for premixing components (a), (b) and (d) faces towards the rotor / stator device, and the apparatus further comprises a chamber; the chamber having an inlet for component (c); said chamber having an outlet for oxidized lignin; Includes.
[0215] A rotor / stator device is a device for processing materials that includes a stator configured as an inner cone with a gear ring. The stator cooperates with a rotor that has arms protruding from a hub. Each of these arms has teeth that mesh with the teeth of the gear ring of the stator. With each revolution of the rotor, the material to be processed is brought outward one stage and subjected to intense shear, mixing and redistribution. The rotor arms and adjacent container chambers of the upright device allow for permanent rearrangement of the material from the inside to the outside, which provides multi-processed dry and / or highly viscous materials with excellent utility for intensive mixing, kneading, fiberization, disintegration and similar processes important in industrial production. The upright positioning of the housing facilitates the falling of the material from the periphery towards the center of the device.
[0216] In one embodiment, the rotor / stator arrangement used in the method according to the invention comprises a stator with a gearing and a rotor with teeth that mesh with the teeth of the stator. In this embodiment, the rotor / stator arrangement has the following features: between the arms of the rotor protrudes a guide funnel that concentrates the material flow entering from above in the central area of the vessel. Outside the guide funnel, there is an annular gap that throttles the material flow. The rotor is equipped with a feed screw that delivers it towards the working area of the device. The guide funnel holds the product in the working area of the device and the feed screw increases the material pressure in the central area.
[0217] For details of the rotor / stator arrangement used in one embodiment of the present method, reference may be made to US Patent Application Publication No. 2003 / 0042344(A1), which is incorporated by reference.
[0218] In one embodiment, the method is carried out using one rotor / stator device, in which the mixing of the components and the reaction of the components are carried out in the same rotor / stator device.
[0219] In one embodiment, the method is practiced using two or more rotor / stator devices, where at least one rotor / stator device is used to mix the components and at least one rotor / stator device is used to react the components.
[0220] This process can be divided into two steps. 1. Preparation of lignin mass (a)+(b)+(d). 2. Oxidation of lignin mass
[0221] Typically, two different types of rotor / stator machines are used. 1. Open rotor / stator machine suitable for mixing lignin powder into water at very high concentrations (30-50% by weight). To accommodate high viscosity materials, special auxiliary devices (inlet funnel, screw, etc.) are used and mixing is less intensive. The peripheral speed is low (up to 15 m / s). Can be used as a batch or continuous machine. 2. In-line rotor / stator machines, where the shear forces are very high (up to 55 m / s peripheral speed) creating favorable conditions for very fast chemical reactions. These machines are used continuously.
[0222] In the open rotor / stator system, a highly concentrated (45-50 wt%) lignin / water mass is prepared. The lignin powder is mixed with an appropriate amount of aqueous ammonia and / or alkali base. It is slowly added to the warm water (30-60℃) that is added. It can be done in a batch manner, but it can also be added intermittently or continuously and then continuously fed to the next process.
[0223] The mass formed is maintained at a temperature of about 60 degrees to keep the viscosity as low as possible and make the material pumpable. The hot lignin / water mass, at a pH of 9-12, is then transferred to the oxidation step using a suitable pump, such as a centrifugal pump or other positive displacement pump.
[0224] In one embodiment, the oxidation is carried out in a continuous in-line reaction in a closed rotor / stator system. Aqueous solutions of ammonia and / or alkali base are pumped into the rotor / stator chamber with a dosing pump to generate maximum turbulence / shear, which results in a rapid oxidation reaction. The oxidized material (AOL) leaves the in-line reactor and is collected in a suitable tank.
[0225] Reaction Products The present inventors have surprisingly found that the oxidized lignin prepared has highly desirable reactivity properties and, further, when used in products including in binder compositions, has improved fire resistance properties and improved long term stability over previously known oxidized lignins.
[0226] In addition, oxidized lignin improves hydrophilicity.
[0227] An important parameter regarding the reactivity of the prepared oxidized lignin is the carboxylic acid group content of the oxidized lignin.
[0228] In one embodiment, the prepared oxidized lignin has a carboxylic acid group content of 0.05 to 10 mmol / g, such as 0.1 to 5 mmol / g, such as 0.20 to 2.0 mmol / g, such as 0.40 to 1.5 mmol / g, such as 0.45 to 1.0 mmol / g, based on the dry weight of component (a).
[0229] Another way to express the carboxylic acid group content is to use the average carboxylic acid group content per lignin polymer, calculated as follows:
[0230] Average amount of COOH functional groups = (total number of moles of COOH) / (total number of moles of lignin)
[0231] In one embodiment, the oxidized lignin prepared has an average carboxylic acid group content per polymer of component (a) of more than 1.5 groups, such as more than 2 groups, such as more than 2.5 groups.
[0232] Method III for preparing oxidized lignin The oxidized lignin used as a component for the binder used in the present invention is One or more lignin-containing components (a); component (b) comprising ammonia and / or one or more amine components, and / or salts thereof, and / or alkali and / or alkaline earth metal hydroxides, such as sodium hydroxide and / or potassium hydroxide; component (c) comprising one or more oxidizing agents; Optionally, component (d) in the form of one or more plasticizers; wherein in the mixing / oxidizing step an oxidized mixture is produced, and then in the oxidation step the oxidized mixture is allowed to continue reacting for a residence time of from 1 second to 10 hours, e.g., from 10 seconds to 6 hours, e.g., from 30 seconds to 2 hours.
[0233] Components (a), (b), (c) and (d) are as defined in Process II for preparing oxidized lignin above.
[0234] In one embodiment, the process includes a premixing step in which the ingredients are contacted with each other.
[0235] In the premixing process, the following components are mixed: Component (a) and component (b), or Component (a), component (b), and component (c); or Component (a), component (b) and component (d), or Component (a), component (b), component (c), and component (d); can be brought into contact with each other.
[0236] In one embodiment, the premixing step can be performed as a separate step and can be followed by the mixing / oxidation step. In such an embodiment of the invention, it is particularly advantageous to contact components (a) and (b) and optionally (d) with each other in a premixing step. In the subsequent mixing / oxidation step, component (c) is then added to the premix produced in the premixing step.
[0237] In one embodiment, the premixing step may correspond to the mixing / oxidation step. In this embodiment of the invention, the oxidation step is started simultaneously with mixing of the components, e.g., components (a), (b) and (c). The subsequent residence time may be in the same equipment as that used to carry out the mixing / oxidation step. Such an embodiment of the invention is particularly advantageous when component (c) is air.
[0238] The inventors have found that by carrying out the oxidation step after the mixing / oxidation step, preferably without continuous mixing of the reaction mixture, the oxidation rate can be controlled very effectively, and at the same time, the oxidation step following the mixing / oxidation step does not require complex equipment, thus reducing the cost of carrying out the process.
[0239] Another advantage is that the oxidized lignin produced is particularly stable. Another surprising advantage is that the viscosity of the oxidized lignin produced can be very easily adjusted. Another surprising advantage is that the concentration of the oxidized lignin can be very high.
[0240] In one embodiment, the residence time is selected to allow the oxidation reaction to reach a desired extent, preferably complete.
[0241] System I for carrying out method III In one embodiment, a system for implementing the method includes: At least one rotor / stator arrangement; one or more inlets for water and components (a) and (b); One or more outlets of the rotor / stator device; at least one reactor, in particular at least one reaction tube, arranged with at least one or more outlets downstream in the process flow direction; Includes.
[0242] In one embodiment, the system comprises one or more inlets for component (c) and / or component (d).
[0243] In one embodiment, the system includes a premixer.
[0244] The pre-mixing device may include one or more inlets for water and / or component (a) and / or component (b) and / or component (c) and / or component (d).
[0245] In one embodiment of the present invention, the premixing device includes inlets for water, component (a) and component (b).
[0246] In the premixing step, component (c) can also be mixed with the above three components (water, component (a) and component (b)). In that case, the premixing device can have an additional inlet for component (c). If component (c) is air, the premixing device can comprise an open mixing vessel, in which case component (c) is already in contact with the other components (water, component (a) and component (b)) through the opening of the vessel. In this embodiment of the invention, the premixing device can also optionally include an inlet for component (d).
[0247] In one embodiment, the system comprises: the inlets for components (a), (b) and (d) are the inlets of a premixing device, in particular an open rotor / stator device; the system further comprising an additional rotor / stator arrangement; The further rotor / stator arrangement has an inlet for component (c) and the further rotor / stator arrangement has an outlet for oxidized lignin.
[0248] The premixing and mixing / oxidation steps can be performed simultaneously, in which case the premixer and the mixing / oxidizer are a single device, i.e., a rotor / stator device.
[0249] In one embodiment, a rotor / stator arrangement for use in the method of the present invention includes a stator with a gearing and a rotor with teeth that mesh with the teeth of the stator. In this embodiment, the rotor / stator arrangement has the following features: between the arms of the rotor, a guide funnel projects which concentrates the material flow entering from above in a central area of the vessel. The outer surface of the guide funnel has an annular gap which throttles the material flow. The rotor is provided with a feed screw which delivers the product towards the working area of the device. The guide funnel holds the product in the working area of the device and the feed screw increases the material pressure in the central area.
[0250] System II for carrying out method III In one embodiment, a system for performing the method includes: one or more inlets for water, components (a) and (b); At least one mixer-oxidizer having one or more outlets; and at least one mixer / heat exchanger disposed downstream in the process flow direction at least one or more of the outlets, the mixer / heat exchanger including a temperature control device; Includes.
[0251] In one embodiment, the system includes one or more additional inlets for component (c) and / or component (d).
[0252] In one embodiment, the system includes a premixing device.
[0253] The pre-mixing device may include one or more inlets for water and / or component (a) and / or component (b) and / or component (c) and / or component (d).
[0254] In one embodiment, the premixing device includes inlets for water, component (a) and component (b).
[0255] In the premixing step, component (c) can also be mixed with the three aforementioned components (water, component (a) and component (b)). The premixing device can then be equipped with an additional inlet for component (c). If component (c) is air, the premixing device can be made of an open mixing vessel, in which case component (c) is already in contact with the other components (water, component (a) and component (b)) through the openings of the vessel. In this embodiment of the invention, the premixing device can also optionally include an inlet for component (d).
[0256] In one embodiment, the system is configured such that the inlets for components (a), (b) and (d) are inlets to an open rotor-stator arrangement, Thereby, the system further comprises a mixer / heat exchanger having an inlet for component (c) and an outlet for the oxidized lignin.
[0257] It is possible for the premixing and mixing / oxidation steps to occur simultaneously, in which case the premixer and the mixing / oxidizer are a single unit of equipment.
[0258] In one embodiment, a rotor / stator arrangement for use in the method according to the invention includes a stator with a gearing and a rotor with teeth that mesh with the teeth of the stator. In this embodiment, the rotor / stator arrangement has the following features: between the arms of the rotor, a guide funnel projects which concentrates the material flow coming from above in the central region of the vessel. On the outer surface of the guide funnel, there is an annular gap which throttles the material flow. The rotor is provided with a feed screw which delivers it towards the working area of the device. The guide funnel holds the product in the working area of the device and the feed screw increases the material pressure in the central area.
[0259] Of course, other devices can be used as the premixing device. Furthermore, the premixing step can be carried out within the mixer-oxidizer.
[0260] In one embodiment, the mixing and oxidation device is a static mixer. A static mixer is a device for continuously mixing fluid materials without the use of moving parts. One type of static mixer is a plate-type mixer, and another common type of device consists of mixer elements contained in a cylindrical (tube) or square housing.
[0261] In one embodiment, the mixer / heat exchanger is configured as a shell and tube heat exchanger with mixing elements, preferably stationary objects through which the mixture flows, whereby mixing occurs as a result of the flow. The mixer / heat exchanger can be constructed as a plug flow reactor.
[0262] Preferably, the growing substrate product of the present invention comprises at least 90% by weight of man-made vitreous fibers based on the total solids weight of the growing substrate. The advantage of having such an amount of fibers in the growing substrate product is that there are sufficient pores formed between the fibers to allow the growing substrate product to retain water and nutrients and to facilitate cutting, while still allowing plant roots to penetrate the growing substrate product. The remaining solids may consist primarily of binder.
[0263] The growing substrate product is in the form of a coherent mass, i.e., the growing substrate is generally (and is manufactured to be) a coherent matrix of man-made vitreous fibers, and can also be formed by granulating slabs of rock wool and consolidating the granulate. A coherent substrate is a single, unified substrate.
[0264] The growth substrate product of the present invention may optionally contain a wetting agent.
[0265] Wetting agents are those commonly used in the art and may be cationic, anionic or nonionic surfactants.
[0266] The growth substrate product may also contain a non-ionic wetting agent such as Rewopal®.
[0267] The growth substrate product may include an ionic surfactant, more preferably an alkyl ether sulfate surfactant wetting agent. The wetting agent may be an alkali metal alkyl ether sulfate or an ammonium alkyl ether sulfate. Preferably, the wetting agent is a sodium alkyl ether sulfate. Alkyl ether sulfate surfactant wetting agents are commercially available. The wetting agent may also be a linear alkyl benzene sulfonate anionic surfactant.
[0268] Some non-ionic wetting agents wash off from the MMVF substrate over time, therefore it is preferred to use ionic wetting agents, especially anionic wetting agents such as linear alkylbenzene sulfonates.
[0269] Preferably the growth substrate product comprises from 0.01 to 1% by weight of humectant, preferably from 0.05 to 0.5% by weight of humectant, more preferably from 0.1 to 0.3% by weight of humectant.
[0270] However, the inventors have discovered that a wetting agent is not essential for the growth substrate product according to the present invention. This is believed to be due to the nature of the binder composition. Thus, preferably, the growth substrate does not contain a wetting agent. This means that the growth substrate is preferably wetting agent-free, i.e., 0% by weight of wetting agent.
[0271] This has several advantages. First, the number of additives in the growing substrate product can be reduced, which is environmentally advantageous and can also reduce costs. In many cases, wetting agents are made from non-renewable resources, so it is beneficial to avoid their use. Furthermore, wetting agents can be washed out of the growing substrate product. This is problematic as wetting agents can contaminate water sources and must be disposed of properly in accordance with environmental regulations. Also, run-off of the wetting agent can cause variability in the growing process, as it changes the properties of the growing substrate product. Also, wetting agents have the disadvantage of foaming out of the product during use. By not using wetting agents, these problems can be avoided.
[0272] The hydrophilicity of an MMVF substrate sample can be measured by determining the settling time of the sample. To measure the settling time, an MMVF substrate with dimensions of 100×100×65 mm is required. A container of 200×200×200 mm or more is filled with water. The settling time is the time from when the sample first comes into contact with the water surface until it is completely submerged. First, a cross-section of the 100×100 mm sample is placed in contact with the water surface. It is then required to sink a distance of just over 65 mm before it is completely submerged. The faster it sinks, the more hydrophilic it is. An MMVF substrate is considered hydrophilic if it has a settling time of less than 120 seconds. Preferably, the settling time is less than 60 seconds. In practice, the settling time of an MMVF substrate can be a few seconds, such as less than 10 seconds.
[0273] The hydrophilicity of a growth substrate product can be defined in terms of the contact angle with water. Preferably, the MMVF of the growth substrate product is such that the contact angle with water is less than 90°. The contact angle is measured by a sessile drop measurement method. Any method can be used for the sessile drop measurement, for example a contact angle goniometer. In practice, a drop of liquid is placed on a solid surface and an image of the drop is recorded over time. The static contact angle is defined by fitting the Young-Laplace equation around the drop: The contact angle is given by the angle between the calculated drop shape function and the sample surface, and its projection on the drop image is called the baseline. The equilibrium contact angle is used to further evaluate and calculate the surface free energy using the Owens, Wendt, Rabel and Kaeble method. For those skilled in the art, methods for calculating the contact angle of a material with water are well known.
[0274] In the method according to the invention, the growth substrate product is 40-100 kg / m 3 , preferably 45 to 80 kg / m 3 This density range has been found to be optimal for root growth and handling of the product, ensuring that the roots penetrate and that the product is not damaged during handling.
[0275] In the method of the present invention, preferably the growth substrate product has a volume in the range of 0.003 to 87 liters, for example 0.005 to 30 liters, preferably 0.008 to 20 liters. The growth substrate product may be in the form of a product conventionally known as a plug, or in the form of a product conventionally known as a block, or in the form of a product conventionally known as a slab.
[0276] Preferably, the growing substrate product has a height in the range of 10mm to 200mm.
[0277] The growth substrate product may have conventional dimensions, such as those commonly known as plugs, with dimensions ranging from 20 to 35 mm, often 25 to 28 mm in height, and 15 to 25 mm in length and width, often around 20 mm, in which case the substrate is often substantially cylindrical, with the ends of the cylinder forming the upper and lower surfaces of the growth substrate.
[0278] The volume of the growth substrate product in plug form is preferably 150 cm 3 Generally, the volume of the plug-shaped growth substrate product is 3 to 150 cm. 3 Preferably in the range of 100 cm3 Less than or equal to 80cm, preferably 3 Less than 75cm, especially preferred 3 Less than or equal to 70cm, most preferably 3 The shortest distance between the upper surface and the lower surface of the plug is preferably 60 mm or less, more preferably 50 mm or less, and particularly preferably 40 mm or less.
[0279] Another embodiment of the plug has a height of 30-50 mm, often around 40 mm, and a length and width in the range of 20-40 mm, often around 30 mm. The growth substrate in this case is often of cubic shape. In the first case, the volume of the growth substrate is 50 cm 3 May be less than 40cm, preferably 40cm 3 The following is the result.
[0280] The growth substrate may be a plug of the type described in this publication, WO 2010 / 003677, as the first coherent MMVF growth substrate. In this case, the volume of the growth substrate product is most preferably between 10 and 40 cm. 3 The range is.
[0281] The growing substrate product may have conventional dimensions, such as those commonly known as blocks. It may have a height of 5-20 cm, often 6-15 cm, and a length and width in the range of 4-30 cm, often 10-20 cm. In this case, the substrate is often substantially cubic. The volume of a growing substrate product in block form is preferably 64-8000 cm. 3 The range is.
[0282] The growing substrate product may have conventional dimensions, such as the product commonly known as a slab. It may have a height ranging from 5 to 15 cm, often 7.5 to 12.5 cm, a width ranging from 5 to 30 cm, often 12 to 24 cm, and a length ranging from 30 to 240 cm, often 40 to 200 cm. In this case, the substrate is often substantially cubic. The volume of the growing substrate product in slab form is preferably 750 to 86,400 cm.3 The range is.
[0283] Growth substrate products are available in sizes from 3 to 300 cm 3 It may be a cube having dimensions of 4 cm x 4 cm x 4 cm. The growth substrate product may also be cylindrical. Preferably it has a length of 50 mm and a diameter of 46 mm, or a length of 40 mm and a diameter of 36 mm, or a length of 27 mm and a diameter of 22 mm.
[0284] In general, the growth substrate product may be of any suitable shape, including cylindrical, cubical and cuboid. Typically, the upper and lower surfaces are substantially planar.
[0285] In the present invention, the term "height" refers to the distance from the bottom surface to the top surface when the substrate is in use. The top surface is the surface that faces upward when the product is placed in its intended use, and the bottom surface is the surface that faces downward when the product is placed in its intended use (and on which the product rests). "Length" refers to the longest distance between two sides, i.e., the distance from one end to the other end when the substrate is in use. The term "width" refers to the distance between two sides perpendicular to the length. These terms have their usual meaning in the art.
[0286] The growing substrate product of the present invention may or may not have a seed hole. The term seed hole has its normal meaning in the art and may also be called a plant hole or cavity. A seed hole is a depression in the upper surface of the growing substrate into which a seed, seedling, cutting or plant is placed.
[0287] Preferably, the growth substrate product includes a liquid-impermeable coating that surrounds at least the sides of the substrate. Preferably, the liquid-impermeable coating is plastic. The growth substrate product may include a liquid-impermeable coating that encases the entire substrate, the coating having at least one opening for a drain hole and at least one opening on the top surface that allows contact between the growth substrate and a further growth substrate.
[0288] The terms seeds, seedlings, cuttings and plants have their usual meaning in the art. The seeds, seedlings, cuttings and plants may be of perennial plants such as cucumber, tomato, eggplant, pepper, strawberry, lettuce, rose; Gerbera or medicinal cannabis.
[0289] In the method of the present invention, the growing substrate product is irrigated, preferably with water and nutrients, which can be done using any of the methods known to those skilled in the art.
[0290] In the present invention, the seed, seedling, cutting or plant is placed in contact with the growing substrate product. This means that the seed, seedling, cutting or plant can be placed directly in the substrate, for example in a seed hole. Alternatively, it can be placed, for example, from a further growing substrate so that it grows in the substrate. Any part of the seed, seedling, cutting or plant can be in contact with any part of the growing substrate product.
[0291] The present invention also relates to a coherent growth substrate product comprising man-made vitreous fibers (MMVF) bound with a cured binder composition, the binder composition prior to curing comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers. Includes.
[0292] The coherent growth substrate product is as described above. This embodiment relates to the method of the present invention. The present invention may have any of the preferred features described above.
[0293] The present invention also relates to an array of two or more coherent growth substrate products, the coherent growth substrate products comprising man-made vitreous fibers (MMVF) combined with a cured binder composition, the binder composition prior to curing comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers. Includes.
[0294] In this embodiment, the one or more coherent growth substrate products can have any of the preferred features described above for the method of the present invention.
[0295] In the array according to the invention, at least two coherent growth substrate products may be identical, for example two identical coherent growth substrate products arranged next to each other, or at least two growth substrate products may not be identical.
[0296] Preferably, the array comprises one growth substrate product positioned in contact with a second growth substrate product. Preferably, one growth substrate is positioned on the top surface of the second growth substrate, for example in a plug / block, block / slab, block / block, plug / block / slab or plug / block / block arrangement. In a plug / block arrangement, a substrate described as a plug above is positioned in contact with a substrate described as a block above. For example, a plug may be inserted into a cavity in a block. In a block / slab arrangement, a substrate described as a block above is positioned in contact with a substrate described as a slab above. For example, a block is positioned on the top surface of a slab. In a block, block arrangement, a block may be positioned in contact with another block, for example, on the top surface of the other block. In a plug, block, slab arrangement, a plug is positioned in contact with a block, which is positioned in contact with a slab. This is also the case in a plug / block / block arrangement. A plug is placed in contact with another block, which is in turn placed in contact with a block.
[0297] The present invention also relates to the use of a coherent growth substrate product for growing plants, the coherent growth substrate product comprising man-made vitreous fiber (MMVF) combined with a hardened aqueous binder composition, the aqueous binder composition before hardening comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers. Includes.
[0298] This embodiment of the invention may have any of the additional features described above for the method of the invention.
[0299] The present invention also provides (i) providing an MMVF; (ii) spraying the MMVF with an aqueous binder composition; (iii) recovering and solidifying the MMVF; and (iv) curing the aqueous binder composition; and the aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; The present invention relates to a method for producing a growth substrate product, comprising:
[0300] This embodiment of the invention may have any of the additional features described above for the method of the invention or the growth substrate of the invention.
[0301] The synthetic vitreous fibers can be produced from a mineral melt, which is provided in a conventional manner by first providing the mineral materials and melting them in a furnace, which can be any of the known types of furnaces for producing melts for MMVF, for example shaft furnaces such as cupola furnaces, tank furnaces or cyclone furnaces.
[0302] Any suitable method can be used to form MMVF from the melt by fiberization. Fiberization can be performed by the spinning cup process, where the melt is centrifugally extruded through orifices in the wall of a rotating cup (spinning cup, also known as an internal centrifuge). Alternatively, fiberization can be performed by centrifugal fiberization, where the melt is projected onto the outer surface of a fiberization rotor and spun, or by a cascade of fiberization rotors (cascade spinner) rotating about a generally horizontal axis.
[0303] In this manner, the melt is entrained in air and formed into a fiber cloud that is collected as a web on a conveyor and carried away from the fiberizer. The fiber web is then consolidated by cross wrapping and / or longitudinal compression and / or vertical compression and / or winding around a mandrel to produce a cylindrical product for pipe insulation. Other consolidation steps may also be performed.
[0304] The binder composition is preferably applied to the fibers as they become airborne and form a cloud, or, although less preferred, can be applied after collection on a conveyor.
[0305] After consolidation, the fiber-to-fiber web is passed through a curing device to cure the binder.
[0306] In one embodiment, the curing is carried out at a temperature of from 100 to 300°C, such as from 170 to 270°C, such as from 180 to 250°C, such as from 190 to 230°C.
[0307] In a preferred embodiment, the curing is carried out in a conventional curing oven for rock wool production, preferably operating at a temperature of 150-300°C, such as 170-270°C, for example 180-250°C, for example 190-230°C.
[0308] In one embodiment, curing is carried out for a time period of from 30 seconds to 20 minutes, such as from 1 to 15 minutes, for example from 2 to 10 minutes.
[0309] In a typical embodiment, curing is carried out at a temperature of 150-250° C. for 30 seconds to 20 minutes.
[0310] The curing process may begin immediately after the binder is applied to the fibers. Curing is defined as a process in which the binder composition undergoes a physical and / or chemical reaction, which in the case of a chemical reaction usually increases the molecular weight of the compounds in the binder composition, thereby increasing the viscosity of the binder composition, usually until the binder composition reaches a solid state. The cured binder composition bonds the fibers to form a matrix of cohesive fiber structures.
[0311] In one embodiment, the curing of the binder in contact with the mineral fibers is carried out in a heat press.
[0312] Curing the binder in contact with the mineral fibres during hot pressing has the particular advantage that it allows the production of a high density product.
[0313] In one embodiment, the curing step comprises drying by pressure, which can be applied by blowing air or gas through / onto the mixture of mineral fibers and binder. EXAMPLES
[0314] Example 1 - Phytotoxicity The phytotoxicity of the binders according to the present invention was compared with that of the PUF binder. Each binder was diluted to various concentrations in nutrient solutions. Cucumber plants were then grown using these solutions. The results are shown in Table 1 below.
[0315] In this test, the length of the first two leaves of cucumber seedlings was measured. The length of this pair of leaves is called the cotyledon length. It was measured based on the one without binder added, which was set as 100%. If the growth of the plant is suppressed by adding the binder, the length of the pair of leaves will be shortened, and the reduction in length will be calculated (see the column on growth suppression).
[0316] The binder of the present invention was prepared as follows: AOL (Ammonia-oxidized lignin): 1000 kg (284 kg lignin UPM BioPiva 100, 57 kg H2O2 (35%), 53 kg NH4OH (24.7%), 506 kg water). Plasticizer (PEG200): 44kg Crosslinker (Primid XL552 - β-hydroxyalkylamide (HAA) crosslinker supplied by EMS-Chemie AG): 22 kg The PUF binder was prepared as follows. Phenol urea formaldehyde resin: 329 liters Water: 1,337 liters Ammonia water: 13 liters Ammonium sulfate: 30.5 liters Momentive Aminosilane VS-142: 1.6 liters The structure of Primid XL552 is as follows:
[0317] [ka]
[0318] [Table 1]
[0319] The results show that there was no effect of pH as the pH of all dilutions used was similar for both binder types tested, therefore the results can be directly compared.
[0320] With regard to phytotoxicity, growth at all tested dilutions of the present invention was better than that of the PUF binder.
[0321] The higher the number, the greater the growth inhibition. For example, when PUF was added at 4%, the growth inhibition was 100% and no plants sprouted. With 4% of the new binder, the growth inhibition was 31.7%, which means that the leaf pair length was 68.3% of the leaf length of the reference plant, so a big improvement compared to PUF.
[0322] Phytotoxicity at higher concentrations is low for the binders of the present invention. Growth was observed at both the 6% and 4% dilutions. However, the PUF binder shows no growth at all for these dilutions.
[0323] At lower concentrations, the binder of the present invention performs slightly better compared to the PUF binder.
[0324] Example 2 - Compressive strength Six different substrates were prepared and their compressive strength was analyzed.
[0325] Product 1: 2.1% by weight of formaldehyde-free binder according to the invention; density 76 kg / m 3 MMVF grown substrate containing 3.5 liters / ton (0.15% by weight) of wetting agent (Texapon®). The binder for this product was prepared as described in Example 1 above.
[0326] Product 2: 2.1% by weight of formaldehyde-free binder according to the invention; density 76 kg / m 3 MMVF growth substrate with; no wetting agent. The binder in this product is the same as that described in Product 1 above.
[0327] Comparison product 1: 2.6 wt% PUF binder; density 77 kg / m 3 ; Wetting agent (linear a The binder for this product was prepared as described in Example 1 above.
[0328] Comparison product 2: 2.6 wt% PUF binder; density 77 kg / m3 ;MMVF growing substrate with 3.5 liters / tonne of wetting agent (Texapon®). The binder in this product is the same as that described for Comparative Product 1 above.
[0329] Comparison product 3: Formaldehyde-free binder 2.8% by weight; density 78 kg / m 3 ;MMVF grown substrate with 6.7 L / T of wetting agent (linear alkyl sulfonate). The binder for this product was made by reacting together the following:
[0330] 185 kg AAA resin: 239 kg dextrose: 575 kg water: 1.1 kg silane.
[0331] The AAA resin was prepared as follows. 90 kg of diethanolamine (DEA) is charged to a 400I reactor and heated to 60° C. Then 75 kg of tetrahydrophthalic anhydride (THPA) is added. The temperature is increased and held at 130° C. for 1 hour, after which 50 kg of trimellitic anhydride (TMA) is added. The reaction mixture is cooled to 95° C., water is added, and the mixture is stirred for 1 hour.
[0332] Comparison product 4: Formaldehyde-free binder 2.8% by weight; density 78 kg / m 3 MMVF growing medium with wetting agent (Texapon®) 3.5 liters / ton. The binder in this product is the same as Comparative Product 3 above.
[0333] The results are shown in Figures 1A to 1E. Compression was measured in both wet and dry conditions in accordance with the insulation standard EN826 (1996), with the following differences: In EN826, the initial deformation X0 and the ultimate compressive strength σ c , σ e has not been calculated. According to the EN standard for insulation materials, test pieces must be stored and measured at (23±5)℃. In the event of a dispute, rock wool is not considered to be affected, so it shall be stored and measured at (23±2)℃ and (50±5)% RH.
[0334] The amount of binder used in inventive products 1 and 2 is significantly less than the amount used in comparative products 1-4, yet comparable compression results are seen when compared to PUF binders and other formaldehyde-free binders. Thus, comparable compressive strengths are achieved using lower amounts of inventive binder. Increasing the amount of inventive binder to 2.8 wt% is expected to improve compressive strength. However, the ability to achieve comparable compression results with lower amounts also has the advantage of allowing the total amount of binder in the product to be reduced.
[0335] Example 3 - Moisture retention Six products, as defined in Example 2 above, were tested for water retention: Product 1, Product 2, Comparative Product 1, Comparative Product 2, Comparative Product 3, and Comparative Product 4.
[0336] The water retention was measured according to the following test method.
[0337] definition Moisture content, WC: Water content (unit: volume %). (initial) saturation, WC -1 / 2h : The water content (volume %) after a fully saturated test specimen is leaked for 2 hours under the same pressure as a "half-thickness water column."
[0338] W.C. -10 : The water content (volume %) when a fully saturated test specimen becomes stable under a pressure equivalent to a 10 cm water column.
[0339] Resaturation: The moisture content (volume %) when a 50% by volume test piece is resaturated in 0.5 cm of water for 24 hours.
[0340] Water column: The height of the water column beginning at half the thickness of a test specimen or block.
[0341] Device Sand mold for pF determination (pF range 0~2.0 (0~100cm), accuracy: zero setting 2mm / flatness 6mm / scale 1mm). The type of sand used is generally sandblasting quality (FEPA grade F100). Digital altimeter (height) (accuracy 0.1mm, range 0~200mm) Balance (accuracy A: 0.5~600g±0.01g, B:600~3000g±0.01g) Band saw A bucket of 25 litres or more Plastic containers Drain grid Wet mineral wool pillar, height 1000mm, width 200mm
[0342] method Weight immediately after submersion (m wet ), height (h wet ) is measured.
[0343] Place the sample on the sandbox under zero pressure (level controller 100) facing the user. The water column should be at the same height as the sand surface. Measure the weight of the sample after 2 hours.
[0344] The sample is returned to the user on the sandbox and subjected to a pressure equivalent to a 10 cm water column for 24 ± 2 hours. The pressure is applied in three (almost identical) stages, with a 5 minute stabilization period after each stage. The height of the level controller depends on the height of the sample.
[0345] The results are shown in Figure 2.
[0346] The results for Product 1 and Product 2 were comparable, therefore the addition of humectants does not appear to have a significant effect on water retention.
[0347] W.C. -10As shown, both Product 1 and Product 2 according to the invention are significantly wetter than the PUF-containing products (Comparative Products 1 and 2).
[0348] The water properties of Products 1 and 2 are comparable to those of Comparative Products 3 and 4, other formaldehyde-free binders.
[0349] The resaturation rates of all products tested are approximately equal.
[0350] Thus, the products of the present invention exhibit improved water retention compared to PUF binders and comparable water retention compared to alternative formaldehyde-free binders.
[0351] Example 4 - Vertical water distribution Six products as defined above under Example 1 were tested for height water distribution. The results are shown in Figure 3. The water distribution was measured according to the following method.
[0352] Submerge the sample in a container filled with tap water (20°C ± 1°C). Then, using a mineral wool column and a balance, adjust the moisture content of the sample to 50% (v / v). The weight of 50% (v / v) is calculated based on the volume of the sample, using the weight and height of the wet sample.
[0353] A moisture sensor and handheld reader are used to measure moisture every 1.5 cm along the height of the sample.
[0354] As can be seen, the moisture distribution across the height of the product of the present invention was comparable to products using PUF binder or another formaldehyde-free binder.
[0355] Example 5 A binder as used in the growth substrate of the present invention was prepared as follows. 3267 kg of water are charged into a 6000 liter reactor, followed by 287 kg of aqueous ammonia (24.7%). 1531 kg of lignin UPM BioPiva 100 are then added slowly over 30 to 45 minutes. The mixture is heated to 40°C and kept at that temperature for 1 hour. After 1 hour, the insolubilized lignin is checked. This is done by placing the solution on a glass plate or a Hegman gauge. The insolubilized lignin is visible as small particles in a brown binder. During the dissolution process, the lignin solution changes from brown to shiny black.
[0356] After the lignin is completely dissolved, 1 liter of firefighting foam (Skumdaemper 11-10 from NCÅ-Verodan) is added. The batch temperature is maintained at 40°C.
[0357] Next, begin adding 307.5 kg of 35% hydrogen peroxide. The hydrogen peroxide is dosed at a rate of 200-300 liters per hour. The first half of the hydrogen peroxide is added at a rate of 200 liters per hour, then the dosage rate is increased to 300 liters per hour.
[0358] During the addition of hydrogen peroxide, the temperature in the reaction mixture is controlled by heating or cooling so that a final reaction temperature of 65°C is reached.
[0359] After reacting at 65°C for 15 minutes, the reaction mixture is cooled to below 50°C, thereby obtaining a resin with a COOH value of 1.2 mmol / (g solid content).
[0360] A binder was prepared from the AOL resin above by adding 270 kg of polyethylene glycol 200 and 433 kg of a 31% aqueous solution of Primid XL-552.
[0361] The final binder exhibited the following analytical data: Solid content: 18.9%; pH: 9.7; Viscosity: 25.5mPas.s; Density: 1.066kg / l
[0362] Lignin oxidation example Example I Example IA - Lignin oxidation in aqueous ammonia with hydrogen peroxide The amounts of ingredients used according to Example IA are shown in Tables IA 1.1 and IA 1.2. Kraft lignin is soluble in water at a relatively high pH, but it is known that the solution viscosity increases significantly at a certain weight percentage. The reason for this increase in viscosity is generally believed to be a combination of strong hydrogen bonds and π electron interactions in the many aromatic rings present in lignin. A rapid increase in viscosity was observed at approximately 21-22% by weight of kraft lignin in water, and 19% by weight of kraft lignin was used in this example.
[0363] In the pH adjustment step, aqueous ammonia was used as the base. The amount was fixed at 4 wt.% based on the total reaction weight. After the pH adjustment step, the pH at the start of the oxidation was 10.7.
[0364] Table IA2 shows the results of CHNS elemental analysis of kraft lignin before and after oxidation. Prior to the analysis, it was heat-treated at 160 °C to remove adsorbed ammonia. The analysis confirmed that a certain amount of nitrogen became part of the oxidized lignin structure during the oxidation process.
[0365] During testing in batch experiments, it was found that adding hydrogen peroxide in full over a short time interval was beneficial for the oxidation, as opposed to adding it in small amounts over a long period of time. In this example, 2.0 wt. % H2O2 was used based on the total reaction weight.
[0366] The oxidation is an exothermic reaction, and a temperature increase is observed upon addition of peroxide. In this example, the temperature was maintained at 60° C. for the 3 hour reaction.
[0367] After oxidation, 31 The amount of lignin functional groups per gram of sample, as determined by P-NMR and aqueous titration, increased. 31Samples for P-NMR were prepared using 2-chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphosphorane (TMDP) as the phosphorylating agent and cholesterol as the internal standard. NMR spectra of kraft lignin before and after oxidation were obtained and the results are summarized in Table IA3.
[0368] The change in COOH groups was determined using aqueous titration and the following equation:
[0369]
number
[0370] Here, V 2S and V 1S is the end volume of the sample, V 2b and V 1b is the volume of the blank. C acid is 0.1M HCl in this case, and m s is the weight of the sample. The values obtained by aqueous titration before and after oxidation are given in Table IA4.
[0371] The average COOH functionality can also be quantified by the saponification number, which represents the number of milligrams of KOH required to saponify 1 gram of lignin. Such a method can be found in AOCS Official Method Cd 3-25.
[0372] The average molecular weight was also measured before and after oxidation using a PSS PolarSil column (9:1 (v / v) dimethylsulfoxide / water solvent, 0.05 M LiBr) and a UV detector at 280 nm. The combination of COOH concentration and average molecular weight also allowed the calculation of the average carboxylic acid content per lignin polymer, and the results are shown in Table IA5.
[0373] Example IB - Lignin oxidation in ammonia with hydrogen peroxide upscaled to pilot scale Lignin oxidation with hydrogen peroxide is an exothermic process, and even at lab scale, a significant temperature increase was observed with the addition of peroxide. This is a natural concern when scaling up chemical processes, since heat generation is related to the cube (volume), while cooling typically scales only with the square (area). Furthermore, the high viscosity of the adhesive intermediates makes it difficult to apply pressure to the protons. Process equipment must be carefully selected and designed. Thus, scale-up was carefully performed and carried out in several steps.
[0374] The first scale-up step was performed using a dedicated stainless steel mixer, which provides very efficient mechanical mixing, from 1 L (lab scale) to 9 L. The scale-up resulted in slightly higher final temperatures than the lab scale, which was due to efficient air cooling of the reactor and slow addition of hydrogen peroxide.
[0375] The next scale-up step was carried out in a 200 L closed reactor equipped with a highly efficient water jacket and a highly efficient propeller agitator. The scale was now 180 L, and hydrogen peroxide was added in two steps, approximately 30 minutes apart. This upscaling went relatively well, but considerable foaming was an issue due to the high reactor loading. To control foaming, a small amount of food-grade antifoam was sprayed during foaming. Most importantly, temperature control was possible, and a final temperature below 70°C could be obtained using external water cooling.
[0376] The pilot scale reaction was carried out in an 800 L reactor with a water-cooled jacket and twin-blade propeller agitation. 158 kg of lignin (UPM LignoBoost™ BioPiva 100) with a dry matter content of 67% by weight was de-lumped and suspended in 224 kg of water and stirred to form a homogenous suspension. With continued stirring, 103 kg of 25% aqueous ammonia was charged to the reactor and stirred for an additional 2 hours to obtain a dark lignin viscous solution.
[0377] To the stirred lignin solution was added 140 kg of 7.5 wt% hydrogen peroxide at 20-25°C over 15 minutes. The temperature and foam level were closely monitored during and after the hydrogen peroxide addition, and cooling water was added to the cooling jacket to maintain acceptable foam levels, a temperature increase of less than 4°C per minute, and a final temperature of less than 70°C. After the temperature stopped increasing, cooling was removed and the product mixture was stirred for an additional 2 hours before being transferred to a shipping container.
[0378] After performing the scale-up, it can be concluded that, even though the reaction is exothermic, most of the heat of reaction is actually absorbed by the heat capacity of the water (enough to raise the water temperature from room temperature to about 60°C) and only the last part has to be removed by cooling. It should be noted that this, together with the short reaction time, makes the process ideal for scale-up and process intensification using continuous reactors such as in-line mixers, tubular reactors or CSTR type reactors. This ensures a more well-defined reaction process with good temperature control.
[0379] Scale-up batch studies have demonstrated that the oxidized lignin produced has properties comparable to those produced in the laboratory batch mode.
[0380] [Table 2]
[0381] [Table 3]
[0382] [Table 4]
[0383] [Table 5]
[0384] [Table 6]
[0385] [Table 7]
[0386] Example II In the following examples, several oxidized lignins were prepared, the following properties of which were determined: Ingredients Solids: The content of each component in a given oxidized lignin solution is based on the anhydrous weight of the component or as described below.
[0387] Kraft lignin is available as a dry powder in BioPiva100 TM The materials were supplied by UPM as supplied. NH4OH 25% was supplied by Sigma-Aldrich and used as supplied. H2O2, 30% (Cas no 7722-84-1) was supplied by Sigma-Aldrich and used as supplied or diluted with water. PEG 200 was supplied by Sigma-Aldrich and used for convenience assumed to be anhydrous. PVA (Mw 89,000-98,000, Mw 85,000-124,000, Mw 130,000, Mw 146,000-186,000) (Cas no Urea (Cas no 57-13-6) was supplied by Sigma-Aldrich and was used as supplied or diluted with water. Glycerol (Cas no 56-81-5) was supplied by Sigma-Aldrich and was used as supplied or diluted with water. Urea (Cas no 57-13-6) was supplied by Sigma-Aldrich and was used as supplied or diluted with water. Glycerol (Cas no 56-81-5) was supplied by Sigma-Aldrich and was used as supplied or diluted with water.
[0388] Oxidized lignin solids The content of oxidized lignin after heating at 200°C for 1 hour is called the "dry solids" and is reported as the weight percent remaining after heating.
[0389] Disk-shaped mineral wool samples (diameter: 5 cm, height: 1 cm) were cut from the mineral wool and heat-treated at 580 °C for at least 30 min to remove organic matter. The solids content of the binder mixture was measured by distributing a sample of the binder mixture (approximately 2 g) onto the heat-treated mineral wool disks in a tin foil container. The weight of the tin foil container containing the mineral wool disks was weighed directly before and after the addition of the binder mixture. Two such mineral wool disks containing the binder mixture in a tin foil container were produced and heat-treated at 200 °C for 1 h. After cooling and storing at room temperature for 10 min, the samples were weighed and the average value of the two dry solids results was calculated.
[0390] COOH group content The change in the COOH group content was determined by aqueous titration and the following formula:
[0391]
number
[0392] Here, V 2S and V 1S is the end volume of the sample, V 2b and V 1b is the volume of the blank sample. C acid In this case, 0.1M HCl, m s,g is the weight of the sample.
[0393] Method for producing oxidized lignin 1) Water and lignin were placed in a three-necked glass flask and mixed at room temperature (20-25°C) while stirring in a water bath connected to a condenser and a temperature recorder. The mixture was stirred for 1 hour. 2) Ammonia was added in one portion during stirring. 3) If the temperature did not rise due to a slightly exothermic reaction with ammonia, heat it up to 35°C. 4) The pH was measured. 5) Plasticizer PEG200 was added and stirred for 10 minutes. 6) After about an hour, when the lignin had completely dissolved, 30% H2O2 was added slowly in one portion. 7) The temperature in the glass-bottom flask rose due to the exothermic reaction caused by the addition of H2O2. If the reaction temperature was lower than 60°C, the temperature was raised to 60°C and the flask was left at 60°C for 1 hour. 8) The round-bottom flask was then removed from the water bath and allowed to cool to room temperature. 9) Samples were taken out and the dry solids, COOH, viscosity, density and pH were measured.
[0394] Oxidized lignin composition Below, the item numbers of the oxidized lignin examples correspond to the item numbers used in Table II.
[0395] Example IIA 71.0 g of lignin UPM Biopiva 100 was dissolved in 149.0 g of water at 20°C, 13.3 g of 25% NH4OH was added, and the mixture was stirred for 1 h on a magnetic stirrer, after which 16.8 g of H2O2 (30%) was added slowly while stirring. The temperature was raised to 60°C in a water bath. After 1 h of oxidation, the water bath was cooled and the reaction was stopped. The resulting material was analyzed for COOH, dry solids, pH, viscosity and density.
[0396] Example IIE 71.0 g of lignin UPM Biopiva 100 was dissolved in 88.8 g of water at 20°C, 13.3 g of 25% NH4OH was added and stirred for 1 h on a magnetic stirrer. 22.8 g of PEG 200 was added and stirred for 10 min, after which 16.7 g of H2O2 (30%) was added slowly with stirring. The mixture was heated to 60°C in a water bath. After 1 h of oxidation, the water bath was cooled and the reaction was stopped. The resulting material was analyzed for COOH, dry solids, pH, viscosity and density.
[0397] Example IIC 71.0 g of lignin UPM Biopiva 100 was dissolved in 57.1 g of water at 20 °C, 13.3 g of 25% NH4OH was added, and the mixture was stirred for 1 h by mechanical stirring, after which 16.6 g of H2O2 (30%) was added slowly while stirring. The temperature was raised to 60° C. with a water bath. After 1 hour of oxidation, the reaction was stopped by cooling the water bath. The resulting material was analyzed for COOH, dry solids, pH, viscosity and density.
[0398] Example IIF 71.0 g of lignin UPM Biopiva 100 was dissolved in 57.1 g of water at 20°C, 13.3 g of 25% NH4OH was added and stirred with a mechanical stirrer for 1 h. PEG 200, 19.0 g, was added and stirred for 10 min, after which 16.6 g of H2O2 (30%) was added slowly with stirring. The temperature was raised to 60°C in a water bath. After 1 h of oxidation, the water bath was cooled and the reaction was stopped. The resulting material was analyzed for COOH, dry solids, pH, viscosity and density.
[0399] [Table 8]
[0400] Example III 8.5 l of hot water (50° C.) and 1.9 l of NH4OH (24.7%) were mixed, whereupon 9.0 kg lignin (UPM biopiva 100) was added slowly over a period of 10 min under high agitation (660 rpm, 44 Hz), followed by the addition of 9.0 kg lignin.
[0401] The high shear forces caused the temperature to rise. After 30 minutes, 4 liters of hot water was added and the material was stirred for another 15 minutes. After stirring for 15 minutes, the remaining portion of hot water (5 L) was added and samples were removed for analysis of undissolved lignin using the Hegman scale and for pH measurement.
[0402] This premix was then transferred to a rotor / stator device and a reactor, where oxidation was carried out with H2O2 (17.5% by volume). The reactor used in this case at least partially comprises a reaction tube and a reaction vessel. The dosage of the premix was 150 l / h and H2O2 was dosed at 18 l / h.
[0403] In this example, a Cavitron CD1000 rotor / stator machine was used to carry out the mixing / oxidation step. The rotor / stator machine was operated at 250 Hz (circumferential speed 55 m / s) and the counter pressure was 2 bar. The residence time in the reaction tube was 3.2 minutes and the residence time in the reaction vessel was 2 hours.
[0404] The temperature of the premix was 62°C and increased to 70°C during the oxidation step.
[0405] The final product was analyzed for COOH content, dry solids, pH, viscosity, and residual H2O2.
[0406] [Table 9]
[0407] Example IV 484 L hot water (70°C) and 47.0 L NH4OH (24.7%) were mixed and 224.0 kg lignin (UPM biopiva 100) was added slowly over 15 min with vigorous stirring, followed by addition of 224.0 kg lignin. Samples were removed for Hegman scale analysis of undissolved lignin and pH measurement.
[0408] This premix was then transferred to a static mixer and a mixer / heat exchanger where oxidation was carried out with H2O2 (35% by volume). The dosage of the premix was 600 l / h and H2O2 was dosed at 17.2 l / h. The residence time in the mixer / heat exchanger was 20 min.
[0409] The temperature of the mixture was increased to 95° C. during the oxidation step.
[0410] The final product was analyzed for COOH content, dry solids, pH, viscosity and residual H2O2.
[0411] A binder was prepared based on this AOL: 49.3 g AOL (19.0% solids), 0.8 g primid XL552 (100% solids) and 2.4 g PEG200 (100% solids) were mixed with 0.8 g water to obtain 19% solids; and used for mechanical property testing in bar tests.
[0412] Bar Examination The mechanical strength of the binders was determined by bar testing: for each binder, 16 bars were produced from a mixture of binder and mineral wool shot from the mineral wool spinning production.
[0413] A sample (16.0 g) of this binder solution with 15% dry solids was mixed thoroughly with the shot (80.0 g). The resulting mixture was then filled into four slots of a heat-resistant silicone form for making small bars (4 x 5 slots per form; slot top dimensions: length = 5.6 cm, width = 2.5 cm; slot bottom dimensions: length = 5.3 cm, width = 2.2 cm; slot height = 1.1 cm). The mixture in the slot was then pressed with a flat metal bar of appropriate size to make the surface of the bars even. Sixteen bars were made from each binder in this way. The resulting bars were then cured at 200°C. The curing time was 1 hour. After cooling to room temperature, they were carefully removed from the container. Five of them were aged in a water bath at 80°C for 3 hours.
[0414] After drying for 1-2 days, the aged bar and five unaged bars were subjected to a three-point bending test (test speed: 10.0 mm / min, break level: 50%, nominal strength: 30 N / mm 2 , Support distance: 40mm, Maximum deflection length: 20mm, Nominal e-module 10000N / mm 2 ) was performed to check its mechanical strength. The bars were placed in the machine with the "top" side up (i.e. the side with dimensions length=5.6 cm, width=2.5 cm).
[0415] [Table 10]
[0416] Other embodiments of the present invention include the following. [1] providing at least one coherent growth substrate product comprising man-made vitreous fiber (MMVF) bound with a cured aqueous binder composition; placing one or more seeds, seedlings, cuttings or plants in contact with the growing substrate product; and watering the growing substrate product; The aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; 1. A method for growing plants in a coherent growth substrate product comprising: [2] The method according to [1], wherein component (i) is in the form of one or more ammonia-oxidized lignins (AOLs). [3] The method according to [1] or [2], wherein component (ii) comprises one or more crosslinkers selected from a β-hydroxyalkylamide crosslinker and / or an oxazoline crosslinker. [4] The component (ii) One or more crosslinkers selected from the group consisting of polyethyleneimine, polyvinylamine, and aliphatic amines; and / or one or more crosslinkers in the form of aliphatic amides; and / or one or more crosslinkers selected from the group consisting of dimethoxyethanal, glycolaldehyde, glyoxylic acid; and / or one or more crosslinkers selected from polyester polyols such as polycaprolactone; and / or one or more cross-linking agents selected from the group consisting of starch, modified starch, CMC; and / or one or more crosslinkers in the form of aliphatic polyfunctional carbodiimides; and / or one or more crosslinkers selected from melamine-based crosslinkers, such as hexakis(methylmethoxy)melamine (HMMM)-based crosslinkers; The method according to any one of [1] to [3], [5] The method according to any of [1] to [4], wherein the component (ii) is contained in an amount of 1 to 40% by weight, for example, 4 to 20% by weight, for example, 6 to 12% by weight, based on the dry weight of the component (i). [6] The method according to any one of [1] to [5], wherein the component (iii) contains one or more plasticizers selected from the group consisting of polyethylene glycol, polyethylene glycol ether, polyether, hydrogenated sugar, phthalate ester, and / or acid such as adipic acid, vanillic acid, lactic acid, and / or ferulic acid, acrylic polymer, polyvinyl alcohol, polyurethane dispersion, ethylene carbonate, propylene carbonate, lactone, lactam, lactide, acrylic polymer having a free carboxy group, and / or polyurethane dispersion having a free carboxy group. [7] The component (iii) One or more plasticizers selected from the group consisting of fatty alcohols, monohydroxy alcohols such as pentanol, and stearyl alcohol; and / or One or more plasticizers selected from the group consisting of alkoxylates, such as ethoxylates, such as butanol ethoxylate, such as butoxytriglycol; and / or One or more plasticizers in the form of propylene glycol; and / or One or more plasticizers in the form of glycol esters; and / or one or more plasticizers selected from the group consisting of adipates, acetates, benzoates, cyclobenzoates, citrates, stearates, sorbates, sebacates, azelates, butyrates, and valerates; and / or One or more plasticizers selected from the group consisting of phenol derivatives, such as alkyl or aryl substituted phenols; and / or one or more plasticizers selected from the group consisting of silanols and siloxanes; and / or One or more plasticizers selected from the group consisting of sulfates, such as alkyl sulfates, sulfonates, such as alkylaryl sulfonates, and / or the like; and / or sulfonates, and phosphates, such as tripolyphosphates; and / or one or more plasticizers in the form of hydroxy acids; and / or One or more plasticizers selected from the group consisting of monomeric amides, such as acetamides, benzamides, fatty acid amides, such as tall oil amides; and / or one or more plasticizers selected from the group consisting of quaternary ammonium compounds such as trimethylglycine, distearyl dimethyl ammonium chloride; and / or one or more plasticizers selected from the group consisting of vegetable oils such as castor oil, palm oil, linseed oil, tall oil, soybean oil; and / or one or more plasticizers selected from the group consisting of hydrogenated oils and acetylated oils; and / or one or more plasticizers selected from the group consisting of methyl esters of one or more plasticizers selected from the group consisting of alkyl polyglucosides, gluconamides, aminoglucosamides, sucrose esters, and sorbitan esters; and / or one or more plasticizers selected from the group consisting of polyethylene glycol and polyethylene glycol ether; The method according to any one of [1] to [6], [8] The component (iii) is 0.5 to 50 based on the dry weight of the component (i). % by weight, preferably 2.5 to 25% by weight, and more preferably 3 to 15% by weight. [9] The method according to any of [1] to [8], wherein the aqueous binder composition further comprises component (iv) in the form of one or more coupling agents, such as organofunctional silanes.
[10] The method according to any of [1] to [9], wherein the aqueous binder composition comprises component (v) in the form of one or more components selected from the group consisting of ammonia, an amine, or any salt thereof.
[11] The method according to any of [1] to
[10] , wherein the aqueous binder composition further comprises a component in the form of urea, particularly in an amount of 5 to 40% by weight, for example 10 to 30% by weight, for example 15 to 25% by weight, based on the dry weight of component (i).
[12] The binder composition essentially comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; Component (iv) in the form of one or more coupling agents, such as organofunctional silanes; Optionally, a component in the form of one or more compounds selected from the group of ammonia, amines or any salts thereof; Optionally, a component in the form of urea; Optionally, a component in the form of a more reactive or non-reactive silicone; Optionally, a hydrocarbon oil; optionally one or more surfactants; water, The method according to any one of [1] to
[11] ,
[13] The method according to any one of [1] to
[12] , wherein the coherent growth substrate product comprises artificial vitreous fibers having a contact angle with water of less than 90°.
[14] The method of any of [1] to
[13] , wherein the coherently grown substrate product comprises man-made vitreous fibers having a geometric mean fiber diameter in the range of 1.5 to 10 microns, preferably 2 to 8 microns, and most preferably 2 to 5 microns.
[15] The method according to any of [1] to
[14] , wherein the growth substrate product has a volume in the range of 0.003 liters to 87 liters.
[16] The method according to any one of [1] to
[15] , wherein the coherent growth substrate product comprises a liquid-impermeable coating.
[17] The method according to any one of [1] to
[16] , wherein the coherent growth substrate product has a height of 10 mm to 150 mm.
[18] The method according to any one of [1] to
[17] , wherein the coherent growth substrate product does not contain any wetting agent.
[19] A cured, aqueous binder composition comprising man-made vitreous fiber (MMVF), The aqueous binder composition before curing is Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; 4. A coherent growth substrate product comprising:
[20] A coherent growth substrate product according to
[19] , further comprising any one of the features described in [2] to
[18] .
[21] An array of two or more coherent growth substrate products, the coherent growth substrate products comprising man-made vitreous fiber (MMVF) bound with a cured aqueous binder composition, the aqueous binder composition prior to curing comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; An array of two or more coherent growth substrate products comprising:
[22] Use of a coherent growth substrate product for growing plants, the coherent growth substrate product comprising man-made vitreous fiber (MMVF) combined with a hardened aqueous binder composition, the aqueous binder composition prior to hardening comprising: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; 1. Use of a coherent growth substrate product for growing plants, comprising:
[23] The use described in
[22] , wherein the coherent growth substrate further has the characteristics described in any one of [2] to
[18] .
[24] (i) providing an MMVF; (ii) spraying the MMVF with an aqueous binder composition; (iii) recovering and solidifying the MMVF; and (iv) curing the aqueous binder composition; and the aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (ii) in the form of one or more crosslinkers; Component (iii) in the form of one or more plasticizers; A method for producing a growth substrate product comprising:
Claims
1. providing at least one coherent growth substrate product comprising man-made vitreous fiber (MMVF) combined with a cured aqueous binder composition; placing one or more seeds, seedlings, cuttings or plants in contact with the growing substrate product; and watering the growing substrate product; The aqueous binder composition before curing comprises: Component (i) in the form of one or more oxidized lignins; Component (iia) in the form of one or more modifiers; 1. A method for growing plants in a coherent growth substrate product comprising:
2. 2. The method of claim 1, wherein said component (i) is in the form of one or more ammonia-oxidized lignins (AOLs).
3. The component (iia) is: Epoxidized oils based on fatty acid triglycerides; Molecules containing three or more epoxy groups; One or more flexible oligomers or polymers containing reactive functional groups, preferably (1) a polymer selected from a low Tg acrylic polymer, a low Tg vinyl polymer, and a low Tg polyether; and / or (2) the reactive functional group selected from a carbodiimide group, an anhydride group, an oxazoline group, an amino group, and an epoxy group; one or more flexible oligomers or polymers containing reactive functional groups, Polyethylenimine, polyvinylamine, or an aliphatic amine; and Aliphatic polyfunctional carbodiimides; The method of claim 1 , further comprising one or more modifiers selected from the group consisting of:
4. 4. The method according to any one of claims 1 to 3, wherein the aqueous binder composition comprises 1 to 40 wt.-%, preferably 4 to 20 wt.-%, more preferably 6 to 12 wt.-%, of component (iia), based on the dry weight of component (i).
5. The aqueous binder composition comprises: Component (ii) in the form of one or more crosslinkers; and / or Component (iii) in the form of one or more plasticizers; The method according to any one of claims 1 to 3, further comprising:
6. The component (ii) is one or more crosslinkers selected from β-hydroxyalkylamide crosslinkers and oxazoline crosslinkers; one or more crosslinkers selected from the group consisting of polyethyleneimine, polyvinylamine, and aliphatic amines; one or more crosslinkers in the form of aliphatic amides; one or more crosslinking agents selected from the group consisting of dimethoxyethanal, glycolaldehyde, and glyoxylic acid; one or more crosslinkers selected from polyester polyols; one or more cross-linking agents selected from the group consisting of starch, modified starch, carboxymethyl cellulose (CMC); One or more crosslinkers in the form of an aliphatic polyfunctional carbodiimide; and one or more crosslinking agents selected from melamine-based crosslinking agents; The method of claim 5 , comprising at least one of:
7. The component (iii) is one or more plasticizers selected from the group consisting of polyethylene glycol, polyethylene glycol ether, polyether, hydrogenated sugar, phthalate ester, acid, acrylic polymer, polyvinyl alcohol, polyurethane dispersion, ethylene carbonate, propylene carbonate, lactone, lactam, lactide, acrylic polymer having a free carboxy group, and polyurethane dispersion having a free carboxy group; one or more plasticizers selected from the group consisting of aliphatic alcohols and monohydroxy alcohols; and / or one or more plasticizers selected from the group consisting of alkoxylates; and / or One or more plasticizers in the form of propylene glycol; and / or One or more plasticizers in the form of glycol esters; and / or one or more plasticizers selected from the group consisting of adipates, acetates, benzoates, cyclobenzoates, citrates, stearates, sorbates, sebacates, azelates, butyrates, and valerates; and / or One or more plasticizers selected from the group consisting of phenol derivatives; and / or one or more plasticizers selected from the group consisting of silanols and siloxanes; and / or One or more plasticizers selected from the group consisting of sulfates, such as alkyl sulfates; and / or phosphates, such as sulfonates, tripolyphosphates; and / or One or more plasticizers in the form of hydroxy acids; and / or one or more plasticizers selected from the group consisting of monomeric amides, benzamides, and fatty acid amides; and / or One or more plasticizers selected from the group consisting of quaternary ammonium compounds such as trimethylglycine, distearyl dimethyl ammonium chloride; and / or One or more plasticizers selected from the group consisting of vegetable oils such as castor oil, palm oil, linseed oil, tall oil, soybean oil; and / or One or more plasticizers selected from the group consisting of hydrogenated oils, acetylated oils; and / or one or more plasticizers selected from the group consisting of methyl esters of one or more plasticizers selected from the group consisting of alkyl polyglucosides, gluconamides, aminoglucosamides, sucrose esters, and sorbitan esters; and / or one or more plasticizers selected from the group consisting of polyethylene glycol and polyethylene glycol ether; The method of claim 5 , comprising at least one of:
8. (a) said component (ii) is present in an amount of 1 to 40% by weight, based on the dry weight of said component (i); and / or (b) said component (iii) is present in an amount of 0.5 to 50% by weight, based on the dry weight of said component (i); The method according to claim 5.
9. The aqueous binder composition comprises: A further component (iv) in the form of one or more coupling agents; Component (v) in the form of one or more members selected from the group of ammonia, amines, or any salt thereof; a further component in the form of urea in an amount of 5 to 40% by weight, for example 10 to 30% by weight, for example 15 to 25% by weight, based on the dry weight of component (i); The method of any preceding claim, further comprising one or more of:
10. The aqueous binder composition essentially comprises: Component (i) in the form of one or more oxidized lignins; Component (iia) in the form of one or more modifiers selected from epoxidized oils based on fatty acid triglycerides; Component (iv) in the form of one or more coupling agents, such as organofunctional silanes; Optionally, a component in the form of one or more compounds selected from the group of ammonia, amines or any salts thereof; Optionally, a component in the form of urea; Optionally, a component in the form of a more reactive or non-reactive silicone; Optionally, a hydrocarbon oil; Optionally, one or more surfactants; and water, The method of claim 1 , comprising:
11. 10. The method of any preceding claim, wherein the coherent growth substrate product comprises man-made vitreous fibers having a contact angle with water of less than 90 degrees.
12. 10. The method of any preceding claim, wherein the coherent growth substrate product comprises man-made vitreous fibers having a geometric mean fiber diameter in the range of 1.5 to 10 microns, preferably 2 to 8 microns, and most preferably 2 to 5 microns.
13. The growth substrate product is a volume ranging from 0.003 liters to 87 liters; and / or Height between 10mm and 150mm; 13. The method of any preceding claim, comprising:
14. 13. The method of any preceding claim, wherein the coherent growth substrate product comprises a liquid impermeable coating.
15. 13. The method of any preceding claim, wherein the coherent growth substrate product does not include any wetting agents.
16. The present invention relates to a cured aqueous binder composition comprising: The aqueous binder composition before curing is A first component (i) in the form of one or more oxidized lignins; and a second component (iia) in the form of one or more modifiers; 4. A coherent growth substrate product comprising:
17. The second component (ii) is Epoxidized oils based on fatty acid triglycerides; Molecules containing three or more epoxy groups; One or more flexible oligomers or polymers containing reactive functional groups, preferably (1) a polymer selected from a low Tg acrylic polymer, a low Tg vinyl polymer, and a low Tg polyether; and / or (2) the reactive functional group selected from a carbodiimide group, an anhydride group, an oxazoline group, an amino group, and an epoxy group; one or more flexible oligomers or polymers containing reactive functional groups, Polyethylenimine, polyvinylamine, or an aliphatic amine; and Aliphatic polyfunctional carbodiimides; 17. The coherent growth substrate article of claim 16, comprising one or more modifiers selected from the group consisting of:
18. 1. An array of two or more coherent growth substrate products, the coherent growth substrate products comprising man-made vitreous fiber (MMVF) combined with a cured aqueous binder composition, the aqueous binder composition prior to curing comprising: A first component (i) in the form of one or more oxidized lignins; and a second component (iia) in the form of one or more modifiers; An array of two or more coherent growth substrate articles comprising:
19. 1. Use of a coherent growth substrate product for growing plants, the coherent growth substrate product comprising man-made vitreous fiber (MMVF) combined with a cured aqueous binder composition, the aqueous binder composition prior to curing comprising: A first component (i) in the form of one or more oxidized lignins; and A second component (iia) in the form of one or more modifiers.
1. Use of a coherent growth substrate product for growing plants, comprising:
20. (i) providing a MMVF; (ii) spraying the MMVF with an aqueous binder composition; (iii) recovering and solidifying the MMVF; and (iv) curing the aqueous binder composition; and the aqueous binder composition before curing comprises: A first component (i) in the form of one or more oxidized lignins; and A second component (iia) in the form of one or more modifiers.
23. A method for producing a growth substrate product comprising:
21. A coherent growth substrate product according to claim 16, further comprising the features according to any one of claims 2 to 15.
22. The use according to claim 19, wherein the coherent growth substrate product further comprises the features according to any one of claims 2 to 15.
Citation Information
Patent Citations
Nursery bed for transplanting
JP2006217915A
Culture soil, and greening construction method using the same
JP2009291126A
Hydroponic plant cultivation system using activated carbon fiber and / or carbonized fiber substrates
JP2011515103A
How to grow plants
JP2013536677A
Aqueous binder composition
JP2015512967A